Polyethylene powder and moldings
By adjusting the component ratio and relaxation time in the polyethylene powder, the problems of poor molding processability, uneven mechanical strength and insufficient creep resistance of microporous membranes in the prior art are solved, and high mechanical strength and dimensional stability are achieved and creep-resistant microporous membranes.
Patent Information
- Application Number
- CN202180075515.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-11-26
- Filing Date
- 2021-11-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-11-15
AI Technical Summary
In the prior art, when manufacturing microporous membranes with high mechanical strength, dimensional stability and creep resistance, there are problems such as poor molding processability, uneven mechanical strength, and inability to withstand long-term stresses caused by electrode expansion and contraction.
The three-component approximation was performed using the Carr Purcell Meiboom Gill method in pulsed NMR, and the component ratio and relaxation time in the polyethylene powder were adjusted to meet the specific tangle index and motility-centered component ratio.
It achieves excellent molding processability, mechanical strength, dimensional stability and creep resistance, and is suitable for applications such as separators for batteries.
Smart Images

Figure GDA0004218155020000621 
Figure GDA0004218155020000631
Abstract
Description
Technical Field
[0001] The present invention relates to polyethylene powder and shaped bodies. Background Art
[0002] Ultra-high molecular weight polyethylene powder is molded by various molding methods such as melt drawing, injection molding, extrusion molding, and compression molding, and is used in a variety of applications such as films, sheets, microporous films, fibers, foams, and tubes.
[0003] In recent years, the demand for polyethylene powder for use in microporous membranes and fibers has increased, and in particular, the demand for polyethylene powder as a raw material for separators, which are important components of lithium-ion batteries, lead-acid batteries, and the like, has rapidly expanded.
[0004] Ultra-high molecular weight polyethylene powder has high viscosity when melted and poor molding processability. Therefore, in the case of manufacturing microporous membranes and high-strength fibers, wet extrusion processing is usually used to dissolve it in a specified solvent and perform extrusion processing. During this wet extrusion processing, when the dispersibility of the polyethylene powder in the solvent is poor, the high molecular weight body is partially present in the molded body, thereby causing dimensional unevenness in terms of width, thickness, etc., or generating unmelted materials, resulting in deterioration of the physical properties and appearance of the molded body. Therefore, it is required to improve the dispersibility of the polyethylene powder in the solvent.
[0005] In addition, when a microporous membrane made of polyethylene powder is used as a battery separator, it is necessary to have a function of isolating the positive electrode and the negative electrode to prevent short circuit while allowing only ions to pass through, a shutdown function for blocking the permeation of ions by melting the pores when a large current flows, thereby preventing the battery reaction from running away, that is, a function of blocking the pores at a temperature lower than the temperature of thermal runaway, the so-called fuse effect, and high mechanical strength.
[0006] In recent years, the demand for higher capacity and higher output power has increased rapidly, mainly for automotive batteries, and with this, the battery separator is required to have further improved mechanical strength and dimensional stability. In addition, as the capacity of the electrode increases, the expansion and contraction of the electrode during charging and discharging increases, so for the battery separator, creep resistance that can withstand long-term stress has become more important.
[0007] Patent Document 1 discloses a technique for obtaining a film and a microporous film having high permeability, low heat shrinkage, excellent mechanical strength and heat resistance by using a polyolefin resin containing an ultrahigh molecular weight ethylene polymer having a specific intrinsic viscosity and melting point.
[0008] Patent Document 2 discloses a technology for obtaining a microporous membrane having excellent molding processability, high air permeability and excellent mechanical strength by using a polyethylene resin composition containing an ethylene homopolymer having a specific melt flow rate, a specific molecular weight distribution and a specific elution amount measured by cross-fractionation chromatography.
[0009] Prior art literature
[0010] Patent Literature
[0011] Patent Document 1: Japanese Patent Application Publication No. 2018-090744
[0012] Patent Document 2: Japanese Patent No. 5840743 Summary of the invention
[0013] Problems to be solved by the invention
[0014] However, in the technology disclosed in Patent Document 1, although the obtained microporous membrane has excellent mechanical strength and dimensional stability, there are the following problems: no research has been conducted to improve molding processability and creep resistance, the mechanical strength may be uneven, and it may not be able to withstand the long-term stress caused by the expansion and contraction of the electrode accompanying charging and discharging.
[0015] In addition, the technology disclosed in Patent Document 2 achieves both moldability and mechanical strength, but has the problem that no research has been conducted to improve dimensional stability and creep resistance.
[0016] Therefore, an object of the present invention is to provide a polyethylene powder which can achieve both excellent molding processability and high mechanical strength and can provide a microporous film having excellent dimensional stability and creep resistance.
[0017] Means used to solve problems
[0018] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that, when a three-component approximation is performed on the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulsed NMR, a polyethylene powder in which the relaxation time T and the component ratio R of each component satisfy a prescribed relationship can solve the above-mentioned problems of the prior art, thereby completing the present invention.
[0019] That is, the present invention is as follows. [1]
[0021] A polyethylene powder wherein, when a three-component approximation is performed on a free induction decay curve obtained by a Carr Purcell Meiboom Gill method in pulse NMR, the relaxation time T of each component and the abundance ratio R of each component satisfy the following <requirement (1)> and <requirement (2)>.
[0022] <Requirements (1)>
[0023] At 180° C., the entanglement index determined by the following (Formula I) is 12 milliseconds or more and 25 milliseconds or less.
[0024] (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )......(Formula I)
[0025] T α : Relaxation time of the low-mobility component α (milliseconds)
[0026] R α : Existence ratio of component α with low motility (%)
[0027] T β : relaxation time of the component β with medium mobility (milliseconds)
[0028] R β : Existence ratio of component β with intermediate motility (%)
[0029] <Requirements (2)>
[0030] At 180° C., the ratio of the component having intermediate mobility determined from the following (Formula II) is 0.25 or more and 0.5 or less.
[0031] (Ratio of components with medium mobility) = R β / (R α +R β )……(Formula II) [2]
[0033] The polyethylene powder according to the above [1], wherein the abundance ratio R of the components obtained by three-component approximation of the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR is:
[0034] The change rate of the abundance ratio of the component with low mobility at 180° C. is not less than −5% and not more than 10%. [3]
[0036] The polyethylene powder according to the above [1] or [2], wherein the abundance ratio R of the components obtained by three-component approximation of a free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR is:
[0037] The change rate of the abundance ratio of the component with high mobility at 180° C. is 50% or less. [4]
[0039] The polyethylene powder according to any one of [1] to [3] above, wherein the isothermal crystallization time of the polyethylene powder at 125° C. is 5 minutes or less. [5]
[0041] The polyethylene powder according to any one of [1] to [4] above, wherein the polyethylene powder has a viscosity average molecular weight of 200,000 or more and 10,000,000 or less. [6]
[0043] The polyethylene powder according to any one of [1] to [5] above, wherein the polyethylene powder has a median particle size of 50 μm or more and 250 μm or less. [7]
[0045] The polyethylene powder according to any one of [1] to [6] above, wherein the polyethylene powder is used for a battery separator. [8]
[0047] A molded product, wherein the molded product is a molded product of the polyethylene powder according to any one of [1] to [7] above. [9]
[0049] The molded article as described in the above-mentioned [8] is a microporous membrane.
[10]
[0051] The molded article according to the above-mentioned [8], wherein the molded article is a fiber.
[11]
[0053] The molded article according to the above-mentioned [8], wherein the molded article is a battery separator.
[0054] Effects of the Invention
[0055] According to the present invention, there can be provided a polyethylene powder which can achieve both excellent molding processability and high mechanical strength and can provide a microporous membrane having excellent dimensional stability and creep resistance. DETAILED DESCRIPTION
[0056] Hereinafter, a mode for carrying out the present invention (hereinafter also referred to as “the present embodiment”) will be described in detail.
[0057] It should be noted that the following embodiments are examples for explaining the present invention, and are not intended to limit the present invention to the following contents. The present invention can be implemented with various modifications within the scope of the gist of the invention.
[0058] [Polyethylene powder]
[0059] The polyethylene powder of the present embodiment is characterized in that when a three-component approximation is performed on a free induction decay curve obtained by the CarrPurcell MeiboomGill method in pulse NMR, the relaxation time T of each component and the abundance ratio R of each component satisfy the following <requirement (1)> and <requirement (2>).
[0060] In addition, regarding the abundance ratio R (%), the total of the three components is set to 100%.
[0061] <Requirements (1)>
[0062] At 180° C., the entanglement index determined by the following (Formula I) is 12 milliseconds or more and 25 milliseconds or less.
[0063] (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )......(Formula I)
[0064] T α : Relaxation time of the low-mobility component α (milliseconds)
[0065] R α : Existence ratio of component α with low motility (%)
[0066] T β : relaxation time of the component β with medium mobility (milliseconds)
[0067] R β : Existence ratio of component β with intermediate motility (%)
[0068] <Requirements (2)>
[0069] At 180° C., the ratio of the component having intermediate mobility determined from the following (Formula II) is 0.25 or more and 0.5 or less.
[0070] (Ratio of components with medium mobility) = Rβ / (R α +R β ) …… Formula (II)
[0071] The polyethylene powder of the present embodiment has the above-mentioned structure, and thus can achieve the effect of achieving both excellent molding processability and high mechanical strength and obtaining a microporous membrane having excellent dimensional stability and creep resistance.
[0072] Hereinafter, the structure of the polyethylene powder according to the present embodiment will be described.
[0073] The polyethylene powder (hereinafter sometimes simply referred to as “powder”) of the present embodiment is composed of an ethylene-based polymer.
[0074] Examples of the ethylene-based polymer include ethylene homopolymers and copolymers (for example, binary or ternary copolymers) of ethylene and other comonomers copolymerizable with ethylene.
[0075] The bonding form of the copolymer can be random or block.
[0076] The other comonomers are not particularly limited, and examples thereof include α-olefins, vinyl compounds, etc. The other comonomers may be used alone or in combination of two or more.
[0077] There are no particular restrictions on the α-olefins, and examples thereof include α-olefins having 3 to 20 carbon atoms, and specifically include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, 1-tetradecene, etc. Among them, from the viewpoint of further improving the heat resistance and strength of the microporous membrane, the other comonomer is preferably propylene and / or 1-butene.
[0078] The vinyl compound is not particularly limited, and examples thereof include vinylcyclohexane, styrene, and derivatives thereof.
[0079] Furthermore, as other comonomers, non-conjugated polyenes such as 1,5-hexadiene and 1,7-octadiene may be used as necessary.
[0080] (Ratio of components with intermediate entanglement index and mobility at 180°C)
[0081] Evaluation of dynamic viscoelasticity is a known index for estimating entanglement of molecular chains in polyethylene powder.
[0082] In the evaluation of dynamic viscoelasticity, the entanglement degree of the molecular chains is evaluated based on the responsiveness when stress is applied to the resin, so the average entanglement degree of the molecular chains of the entire resin can be obtained. However, when controlling multiple physical properties such as mechanical properties and molding processability at the same time, it is preferred to separately treat the various entangled components present in the resin, so the average entanglement degree of the molecular chains alone is not sufficient as an indicator.
[0083] In order to clarify the raw materials suitable for molded bodies with well-controlled physical properties such as mechanical properties and molding processability, the inventors used the entanglement index calculated from the pulse NMR measurement at 180°C and the proportion of components with medium mobility as indicators that can separately evaluate the entanglement components of various molecular chains present in the resin, and accurately evaluated the entanglement degree of polyethylene powder.
[0084] In the pulse NMR measurement, the Carr Purcell Meiboom Gill method was used, which is a measurement method suitable for evaluating the mobility of polymers whose molecular chains actively move, for example, polymers in a rubbery state.
[0085] As a result, it was found that when a three-component approximation was performed on the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR, polyethylene powder whose relaxation time T and component ratio R of each component simultaneously satisfied the following <Requirement (1)> and <Requirement (2)> was surprisingly suitable as a raw material for a microporous membrane from the perspective of mechanical properties and molding processability.
[0086] <Requirements (1)>
[0087] At 180° C., the entanglement index determined by the following (Formula I) is 12 milliseconds or more and 25 milliseconds or less.
[0088] (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )......(Formula I)
[0089] T α : Relaxation time of the low-mobility component α (milliseconds)
[0090] R α : Existence ratio of component α with low motility (%)
[0091] T β : relaxation time of the component β with medium mobility (milliseconds)
[0092] R β : Existence ratio of component β with intermediate motility (%)
[0093] <Requirements (2)>
[0094] At 180° C., the ratio of the component having intermediate mobility determined from the following (Formula II) is 0.25 or more and 0.5 or less.
[0095] (Ratio of components with medium mobility) = R β / (R α +R β )……(Formula II)
[0096] The polyethylene powder of the present embodiment has an entanglement index determined from the above (Formula I) at 180° C. in the range of 12 to 25 milliseconds, preferably 13 to 22 milliseconds, and more preferably 14 to 20 milliseconds.
[0097] For the polyethylene powder of the present embodiment, when the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulsed NMR is approximated by three components, the component α with low mobility is equivalent to the part with strong molecular chain entanglement in the polyethylene powder, which is considered to be a component that will not be untied during the molding process and is easily retained in the microporous membrane. On the other hand, the component β with intermediate mobility in the polyethylene powder of the present embodiment is equivalent to the part with weaker molecular chain entanglement than the above-mentioned component α with low mobility, which is considered to be a component that is easily untied during the molding process. In addition, the stronger the entanglement of each component, the smaller the value of the relaxation time T.
[0098] When the entanglement index determined from the above formula (I) at 180° C. is 12 milliseconds or more, the stress remaining after the molding process can be reduced, so there is a tendency that a microporous membrane having excellent dimensional stability can be obtained.
[0099] On the other hand, when the entanglement index determined by the above formula (I) at 180°C is 25 milliseconds or less, the molecular chains in the polyethylene powder are more entangled, so that the microporous membrane obtained by molding tends to have high mechanical strength and excellent creep resistance.
[0100] For the polyethylene powder of this embodiment, when a three-component approximation is performed on the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR, the ratio of the component with intermediate mobility at 180°C obtained by the above (Formula II) is greater than 0.25 and less than 0.5, preferably greater than 0.25 and less than 0.45, and more preferably greater than 0.3 and less than 0.4.
[0101] When the ratio of the component having a medium mobility at 180° C. determined from the above (Formula II) is 0.25 or more, the molding processability of the polyethylene powder is improved, and a microporous membrane having excellent appearance tends to be obtained.
[0102] On the other hand, when the ratio of the component having intermediate mobility at 180° C. is 0.5 or less, an appropriate number of entanglement points of molecular chains remain in the microporous membrane obtained by molding, so stress is easily transmitted and creep resistance tends to be excellent.
[0103] Generally, when the degree of entanglement of the polymer molecular chain is strong, the mechanical strength of the obtained microporous membrane is improved, but since the dispersibility of the polymer molecular chain is low, the molding processability is deteriorated, and when it is manufactured into a microporous membrane, uneven thickness, etc. is generated. When there is uneven thickness, etc. of the microporous membrane like this, a portion with weak mechanical strength is generated, which is easy to become the starting point of deterioration.
[0104] On the other hand, when the degree of entanglement of the molecular chains of the polymer is weak, although the molding processability is good, the mechanical strength is reduced.
[0105] Since the polyethylene powder of the present embodiment has well-controlled strength of entanglement of polymer molecular chains, when manufactured into a microporous membrane, both mechanical strength and molding processability can be improved.
[0106] In addition, when there are many entanglement points of the molecular chains of the polymer in the microporous membrane, the mechanical strength is high and the stress is easily transmitted, so the creep resistance is excellent, but due to the large residual stress, there is a tendency for the dimensional stability to deteriorate. When the microporous membrane is used as a separator of a battery, the deterioration of the dimensional stability will lead to short circuit and degradation.
[0107] On the other hand, when there are fewer entanglement points in the molecular chains of the polymer, the dimensional stability becomes excellent, but there is a tendency not to show sufficient mechanical strength. In addition, since stress is difficult to transmit, local loads are easily applied. When the microporous membrane is used as a battery separator, there is a tendency not to be able to withstand the volume changes of the electrode accompanying charging and discharging.
[0108] The polyethylene powder of the present embodiment has excellent dimensional stability and sufficient mechanical strength and creep resistance because the amount of entanglement points of the polymer molecular chains is well controlled.
[0109] In order to make the entanglement index at 180°C obtained by the above (Formula I) and the proportion of the components with intermediate mobility obtained by the above (Formula II) show values within the above-specified range, it is necessary that in the polyethylene powder, the entanglement degree of the strongly entangled molecular chains has a certain strength and the proportion of the weakly entangled molecular chains is high.
[0110] Furthermore, the polyethylene powder that satisfies these requirements has the following characteristics: it contains a plurality of polymer components having different entanglement states.
[0111] Methods for controlling the ratio of components intermediate between the entanglement index at 180°C obtained from the above (Formula I) and the mobility obtained from the above (Formula II) include changing the state of the catalyst during polyethylene polymerization and mixing a plurality of catalyst components having greatly different polymerization behaviors.
[0112] Specifically, the following methods can be cited: using a polymerization catalyst comprising a carrier having large pores and which is easily broken, carrying out polymerization under high pressure conditions in the first half of the polymerization, and then adjusting the slurry concentration in the polymerizer to 40% by mass or more; prepolymerizing a polymerization catalyst comprising a carrier having large pores and which is easily broken, and then setting the stirring speed in the polymerizer to 300 rpm or more; mixing and using a plurality of catalysts having very different distributions of active substances on the carrier surface, etc.
[0113] When synthesizing a polymerization catalyst used in a polymerization reaction of polyethylene, by using a carrier having large pores, the loading amount of active substances in the pores is increased, and in the polymerization reaction of polyethylene, the polymerization of polyethylene in the above-mentioned pores can be promoted. In addition, in the narrow space in the pores, the molecular chains of the growing polyethylene are easily intertwined with each other, so that a component with a strong degree of entanglement of the molecular chains can be polymerized.
[0114] On the other hand, since the support used in the polymerization catalyst has an easily ruptured structure, the catalyst is easily ruptured due to the increase in pressure in the pores accompanying the growth of the molecular chains of the polyethylene during the polymerization of polyethylene.
[0115] Furthermore, when the catalyst is broken by increasing the stirring intensity, the molecular chains of the growing polyethylene become less likely to intertwine with each other, and a component with a weak degree of entanglement of the molecular chains can be polymerized.
[0116] Furthermore, by adding a thickener after the carrier is synthesized and adjusting the pressure difference between the transport source and the transport destination during catalyst transport to be small, the catalyst carrier can be prevented from breaking before the polymerization step, and multiple polyethylene components with different degrees of entanglement of molecular chains can be generated during polymerization.
[0117] The pulse NMR measurement used for the measurement of the polyethylene powder according to the present embodiment is specifically performed by the following method.
[0118] First, a sample tube filled with polyethylene powder to a height of 1 cm from the bottom was placed in a TD-NMR apparatus (model: minispec mq20) manufactured by Bruker set to an internal temperature of 30° C., and the sample tube was heated according to the <temperature increase conditions> shown below.
[0119] The temperature shown in the following <Temperature Increase Condition> is a value obtained by measuring the internal temperature of the sample using a thermocouple.
[0120] <Temperature rising conditions>
[0121] (1) Set to 30°C and let stand for 5 minutes.
[0122] (2) Raise the temperature to 180°C at a rate of 5°C / min.
[0123] (3) After heating to 180°C, let stand for 25 minutes.
[0124] After the temperature increase is completed according to the above procedure, the spin-spin relaxation time (T2, sometimes simply referred to as "relaxation time T" in this specification) of the polyethylene powder is measured under the <measurement conditions> shown below.
[0125] Then, after the measurement was completed, the same measurement was repeated three times, for a total of four measurements.
[0126] <Measurement conditions>
[0127] Magnetic field strength: 0.47T
[0128] Determination of nuclear types: 1 H(20MHz)
[0129] Determination method: Carr Purcell Meiboom Gill method
[0130] Cumulative times: 256 times
[0131] Repeat time: 3 seconds
[0132] The interval between the first 90° pulse and the 180° pulse (τ): 0.04 ms
[0133] Total echo signal number: 6400
[0134] The free induction decay (FID) obtained in the fourth measurement among all the four measurements was subjected to curve fitting using the analysis program TD-NMR-A manufactured by Bruker.
[0135] The function shown in the following <Formula 1> was used for fitting.
[0136] <Formula 1>
[0137] f(t)=R α exp(-t / T α )+R β exp(-t / T β )+R γexp(-t / T γ )
[0138] (Among them, R α +R β +R γ =100)
[0139] t: variable (elapsed time from the start of pulse radiation)
[0140] T α : Relaxation time of the low-mobility component α (milliseconds)
[0141] R α : Existence ratio of component α with low motility (%)
[0142] T β : relaxation time of the component β with medium mobility (milliseconds)
[0143] R β : Existence ratio of component β with intermediate motility (%)
[0144] T γ : Relaxation time of the highly mobile component γ (milliseconds)
[0145] R γ : Existence ratio of component γ with high mobility (%)
[0146] Finally, the entanglement index and the motility-intermediate component ratio were calculated from the relaxation time T and the existence ratio R obtained by curve fitting of the free induction decay using the following (Formula I) and (Formula II).
[0147] (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )(Formula I)
[0148] (Ratio of components with medium mobility) = R β / (R α +R β )(Formula II)
[0149] Generally, in the case of a rubbery polymer in which the molecular chain moves actively, the free induction decay obtained by pulse NMR measurement can be represented by an exponential function. Therefore, in this measurement, the obtained free induction decay can also be fitted as the sum of three different components represented by an exponential function as shown in the above <Formula 1>.
[0150] In addition, it is known 1 The higher the mobility of H, that is, the higher the mobility of the molecular chain, the slower the decay rate of the free induction decay. The relaxation time T in each exponential function is T α <T β <T γ , the component with the lowest mobility is set as α, the component with medium mobility is set as β, and the component with the highest mobility is set as γ.
[0151] In addition, the component α corresponds to the portion where the molecular chains are strongly entangled in the polyethylene powder, the component β corresponds to the portion where the molecular chains are weakly entangled, and the component γ is the portion where the molecular chains are not entangled.
[0152] More specifically, the entanglement index at 180° C. and the ratio of components having intermediate mobility in the present embodiment can be measured by the method described in Examples.
[0153] (Rate of change in abundance ratio of components with low mobility at 180°C)
[0154] For the polyethylene powder of this embodiment, the range of the change rate of the abundance ratio R of the components obtained by performing a three-component approximation on the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR, as the abundance ratio of the component α with low motility at 180°C, is preferably greater than -5% and less than 10%, more preferably greater than -2% and less than 8%, and further preferably greater than 0% and less than 6%.
[0155] The change rate of the abundance ratio of the component with low mobility at 180° C. in the polyethylene powder of the present embodiment is determined by the method shown below.
[0156] When determining the above (the entanglement index at 180°C and the ratio of the component with intermediate mobility), the free induction decay (FID) obtained by the first and fourth measurements in the pulse NMR measurement specifically described above was subjected to curve fitting using the analysis program TD-NMR-A manufactured by Bruker. The function shown in the above <Formula 1> was used for the fitting.
[0157] From the abundance ratio R obtained by fitting, the change rate (%) of the abundance ratio of the component with low mobility is calculated by the following (Formula III).
[0158] (Rate of change in abundance ratio of components with low mobility) = ((R α4 -R α1 ) / R α1 )×100……(Formula III)
[0159] R α1: The presence ratio of component α with low motility at the first measurement
[0160] R α4 : The presence ratio of component α with low motility at the fourth measurement
[0161] The change rate shows a negative value when the molecular chains of the components that are strongly entangled under heating conditions are untangled, and shows a positive value when the molecular chains of the components that are weakly entangled under heating conditions are strongly entangled.
[0162] By making the change rate of the existence ratio of the above-mentioned low-mobility component to be -5% or more, it is easy to leave components with strong entanglement even after molding, and a microporous membrane with better mechanical strength and creep resistance can be obtained. On the other hand, by making the change rate of the existence ratio of the above-mentioned low-mobility component to be 10% or less, the ratio of weakly entangled molecular chains and unentangled molecular chains can be maintained above a certain value, and there is a tendency for excellent molding processability.
[0163] Specifically, the change rate of the abundance ratio of the component with low mobility at 180° C. of the polyethylene powder of the present embodiment can be measured by the method described in Examples.
[0164] The change rate of the abundance ratio of the component with low mobility at 180° C. of the polyethylene powder of the present embodiment can be controlled within the above numerical range by adjusting the concentration and temperature during synthesis of the catalyst carrier to a certain value or more.
[0165] (Change rate of the abundance ratio of components with high mobility at 180°C)
[0166] For the polyethylene powder of the present embodiment, the range of the change rate of the abundance ratio R of the components with high mobility at 180° C., which is obtained by performing a three-component approximation on the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR, is preferably 50% or less, more preferably 10% or less, and further preferably 5% or less. In addition, the lower limit is not particularly limited, but is usually 0% or more.
[0167] The change rate of the abundance ratio of the component with high mobility in the polyethylene powder of the present embodiment is obtained by the method shown below.
[0168] When determining the above (entanglement index at 180°C and the ratio of components with intermediate mobility), curve fitting was performed using the analysis program TD-NMR-A manufactured by Bruker for the free induction decay (FID) obtained by the first and fourth measurements in the pulse NMR measurement specifically described above.
[0169] The function shown in the above <Formula 1> is used for fitting.
[0170] Based on the abundance ratio R obtained by fitting, the change rate (%) of the abundance ratio of the component with high mobility represented by the following (Formula IV) was calculated.
[0171] (Ratio of change in abundance of components with high mobility) = ((R γ4 -R γ1 ) / R γ1 )×100……(Formula IV)
[0172] R γ1 : The abundance ratio of the highly mobile component γ in the first measurement
[0173] R γ4 : The abundance ratio of the highly mobile component γ in the fourth measurement
[0174] The more the molecular chains are untangled under heating conditions, the larger the value of the change rate is.
[0175] When the change rate of the abundance ratio of the component with high mobility is 50% or less, the component having entangled molecular chains is likely to remain even after the molding process, and a microporous membrane having more excellent mechanical strength and creep resistance can be obtained.
[0176] Specifically, the change rate of the abundance ratio of the component with high mobility at 180° C. of the polyethylene powder of the present embodiment can be measured by the method described in Examples.
[0177] The change rate of the abundance ratio of the component with high mobility at 180° C. of the polyethylene powder of the present embodiment can be controlled within the above numerical range by adjusting the slurry concentration and stirring speed during polymerization to appropriate ranges.
[0178] (Isothermal crystallization time at 125°C)
[0179] The isothermal crystallization time of the polyethylene powder of the present embodiment is preferably 5 minutes or less, more preferably 4.5 minutes or less, and even more preferably 4 minutes or less.
[0180] In addition, the lower limit of the isothermal crystallization time is not particularly limited, but is usually 0 minutes or more.
[0181] The isothermal crystallization time at 125° C. of the polyethylene powder of the present embodiment is determined by the method described below using a differential scanning calorimeter (DSC).
[0182] First, the aluminum pan containing the polyethylene powder was placed in a heating furnace and heated according to the following (temperature increase and decrease conditions). The heating was performed in a nitrogen atmosphere.
[0183] <Temperature rise and fall conditions>
[0184] (1) Maintain at 50°C for 1 minute.
[0185] (2) Raise the temperature to 180°C at a rate of 200°C / min.
[0186] (3) Maintain at 180°C for 5 minutes.
[0187] (4) Cool down to 125°C at a rate of 80°C / min.
[0188] Then, the time when the temperature reaches 125° C. is defined as the starting point (0 minute), and the time when the peak top of the exothermic peak due to crystallization is obtained is defined as the isothermal crystallization time at 125° C.
[0189] When the isothermal crystallization time at 125° C. is 5 minutes or less, the component having entangled molecular chains tends to be uniformly present in the molded product, so that stress is easily transmitted, and a microporous membrane having more excellent creep resistance can be obtained.
[0190] Examples of methods for controlling the isothermal crystallization time at 125° C. of the polyethylene powder of this embodiment include uniformly supporting active sites on a catalyst carrier used in the polymerization step of the polyethylene powder and uniformly adjusting the temperature in the polymerization reactor.
[0191] Specifically, the isothermal crystallization time at 125° C. of the polyethylene powder of the present embodiment can be measured by the method described in Examples.
[0192] (Viscosity average molecular weight (Mv))
[0193] The viscosity average molecular weight (Mv) of the polyethylene powder of the present embodiment is preferably 200,000 or more and 10,000,000 or less, more preferably 250,000 or more and 3,000,000 or less, and still more preferably 300,000 or more and 2,000,000 or less.
[0194] The viscosity average molecular weight (Mv) of the polyethylene powder can be controlled within the above numerical range by appropriately adjusting the polymerization conditions and the like described below.
[0195] Specifically, the viscosity average molecular weight (Mv) can be controlled within the above numerical range by allowing hydrogen as a chain transfer agent to exist in the polymerization system or by changing the polymerization temperature.
[0196] Since the viscosity average molecular weight (Mv) of the polyethylene powder of the present embodiment is 200,000 or more, the microporous membrane including the polyethylene powder of the present embodiment has sufficient mechanical strength.
[0197] On the other hand, the polyethylene powder of the present embodiment has a tendency to have excellent dispersibility in solvents, stretchability, and other molding processability by having a viscosity average molecular weight (Mv) of 10,000,000 or less. Therefore, the microporous membrane molded using the polyethylene powder of the present embodiment has uneven thickness, little unmelted material, is less likely to deteriorate, and has an excellent appearance.
[0198] The viscosity average molecular weight (Mv) of the polyethylene powder of the present embodiment can be calculated by the following formula from the intrinsic viscosity [η] (dL / g) determined in accordance with ISO 1628-3 (2010).
[0199] More specifically, it can be measured by the method described in the Examples.
[0200] Mv=(5.34×10 4 )×[η] 1.49
[0201] (Median particle size)
[0202] The median particle size of the polyethylene powder of the present embodiment is preferably in the range of 50 μm or more and 250 μm or less, more preferably 60 μm or more and 200 μm or less, and still more preferably 70 μm or more and 150 μm or less.
[0203] The median particle size of the polyethylene powder of the present embodiment is a particle size (D50) when the cumulative mass reaches 50%.
[0204] When the median particle size is 50 μm or more, the ease of handling of the polyethylene powder in the production process and the extrusion processing process (improvement of fluidity, suppression of dust, etc.) is improved.
[0205] On the other hand, when the median particle size is 250 μm or less, the plasticizer can easily be impregnated into the polyethylene powder, and the molding processability tends to be improved.
[0206] Examples of methods for controlling the median particle size of the polyethylene powder of this embodiment within the above numerical range include: a method of controlling the particle size of the polymerization catalyst; a method of adjusting the polymerization conditions described below so as to suppress rapid polymerization reaction (hereinafter sometimes referred to as rapid polymerization); and the like.
[0207] Specifically, the median particle size of the polyethylene powder according to the present embodiment can be measured by the method described in Examples described later.
[0208] [Method for producing polyethylene powder]
[0209] Hereinafter, the method for producing the polyethylene powder according to the present embodiment will be described.
[0210] (Catalyst component)
[0211] There is no particular limitation on the catalyst component used in the manufacture of the ethylene polymer constituting the polyethylene powder of the present embodiment, and a Ziegler-Natta catalyst or a metallocene catalyst manufactured by the method described in Japanese Patent No. 5782558 and Japanese Patent Application Laid-Open No. 2019-19265 can be used. It is particularly preferred to use a Ziegler-Natta catalyst.
[0212] As the Ziegler-Natta catalyst used for producing the polyethylene powder of the present embodiment, for example, the following olefin polymerization catalyst is preferred, wherein the olefin polymerization catalyst comprises a solid catalyst component [A] and an organometallic compound component [B], wherein the solid catalyst component [A] is produced by supporting an organomagnesium compound (A-4) soluble in an inert hydrocarbon solvent represented by the following (Formula iii) and a titanium compound (A-5) represented by the following (Formula iv) on a carrier (A-3) prepared by reacting an organomagnesium compound (A-1) soluble in an inert hydrocarbon solvent represented by the following (Formula i) and a chlorinating agent (A-2) represented by the following (Formula ii).
[0213] (A-1): (M 1 ) γ (Mg) δ (R 1 ) e (R 2 ) f (OR 3 ) g ...(Formula i)
[0214] (In formula i, M 1 is a metal atom belonging to any one selected from the group consisting of Group 12, Group 13 and Group 14 of the Periodic Table, R 1 , R 2 and R 3 Each is a hydrocarbon group having 1 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers satisfying the following relationship.
[0215] 0≤γ, 0<δ, 0≤e, 0≤f, 0≤g, 0<e+f, 0≤g / (γ+δ)≤2, kγ+2δ=e+f+g (here, k represents M 1 valence.
[0216] (A-2): H h SiCl i R 4 (4-(h+i)) ……(Formula ii)
[0217] (In formula ii, R 4is a hydrocarbon group having 1 or more and 12 or less carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)
[0218] (A-4): (M 2 ) α (Mg) β (R 4 ) a (R 5 ) b Y 1 c ……(Formula iii)
[0219] (In formula iii, M 2 is a metal atom belonging to any one selected from the group consisting of Group 12, Group 13 and Group 14 of the Periodic Table, R 4 and R 5 is a hydrocarbon group having 2 or more and 20 or less carbon atoms, Y 1 is alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 6 ,R 7 、-SR 8 (Here, R 6 , R 7 and R 8 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 (may be different from each other) and any of the β-keto acid residues, α, β, a, b and c are real numbers satisfying the following relationship.
[0220] 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤c / (α+β)≤2, nα+2β=a+b+c (here, n represents M 2 valence.
[0221] (A-5): Ti(OR 9 ) d X 1 (4-d) ……(Formula iv)
[0222] (In formula iv, d is a real number greater than or equal to 0 and less than or equal to 4, R 9 is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)
[0223] First, the organomagnesium compound (A-1) will be described.
[0224] The organomagnesium compound (A-1) is shown in the form of an organomagnesium complex soluble in an inert hydrocarbon solvent, but includes all dihydrocarbylmagnesium compounds and complexes of the compound with other metal compounds.
[0225] The above relationship of the symbols γ, δ, e, f and g in the above (Formula i) kγ+2δ=e+f+g represents the stoichiometry of the valence of the metal atom and the substituent.
[0226] In the above (Formula i), for R 1 , R 2 The hydrocarbon group represented is not particularly limited, and each is independently an alkyl group, a cycloalkyl group or an aryl group, and examples thereof include methyl group, ethyl group, propyl group, butyl group, pentyl group, hexyl group, octyl group, decyl group, cyclohexyl group, and phenyl group.
[0227] Among them, R 1 and R 2 Preferably, each is an alkyl group.
[0228] In the case of γ>0, as the metal atom M 1 A metal atom belonging to any one of the groups consisting of Groups 12, 13 and 14 of the periodic table can be used, and examples thereof include zinc, boron, and aluminum, and aluminum and zinc are particularly preferred.
[0229] For magnesium relative to metal atoms M 1 The ratio δ / γ is not particularly limited, but is preferably 0.1 or more and 30 or less, and more preferably 0.5 or more and 10 or less.
[0230] When a predetermined organomagnesium compound having γ=0 is used as (A-1), for example, in R 1 In the case of 1-methylpropyl or the like, it is soluble in an inert hydrocarbon solvent, and such a compound also gives a preferable result in the production of the polyethylene powder of the present embodiment.
[0231] In the above (Formula i), the hydrocarbon group R in the case of γ=0 is 1 , R 2 Any one of the following three groups (1), (2), and (3) is preferred.
[0232] Group (1):
[0233] R 1 and R 2 At least one of them is a secondary or tertiary alkyl group having 4 or more and 6 or less carbon atoms. 1 and R 2 All of them are alkyl groups having 4 to 6 carbon atoms, and at least one of them is a secondary or tertiary alkyl group.
[0234] Group (2):
[0235] R 1 and R 2 are alkyl groups with different carbon number. 1 is an alkyl group having 2 or 3 carbon atoms, and R 2 It is an alkyl group having 4 or more carbon atoms.
[0236] Group (3):
[0237] R 1 and R 2 At least one of them is a hydrocarbon group having 6 or more carbon atoms. 1 and R 2 The total number of carbon atoms contained in the alkyl group is 12 or more.
[0238] The following specifically shows the hydrocarbon group R in the case where γ=0 in the above (Formula i). 1 , R 2 .
[0239] Examples of the secondary or tertiary alkyl group having 4 to 6 carbon atoms in group (1) include 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, and 2-methyl-2-ethylpropyl. 1-methylpropyl is particularly preferred.
[0240] In addition, examples of the alkyl group having 2 or 3 carbon atoms in group (2) include ethyl group, 1-methylethyl group, propyl group and the like.
[0241] The ethyl group is particularly preferred.
[0242] The alkyl group having 4 or more carbon atoms is not particularly limited, and examples thereof include butyl, pentyl, hexyl, heptyl, and octyl groups.
[0243] A butyl group and a hexyl group are particularly preferred.
[0244] In addition, the hydrocarbon group having 6 or more carbon atoms in group (3) is not particularly limited, and examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, 2-naphthyl, etc. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are more preferred.
[0245] Generally, as the number of carbon atoms contained in the alkyl group increases, it tends to be easily dissolved in an inert hydrocarbon solvent and the viscosity of the solution tends to increase. 1 , R 2It should be noted that the organomagnesium compound (A-1) is used in the form of an inert hydrocarbon solution, but it can be used without problems even if a trace amount of Lewis basic compounds such as ethers, esters, and amines are contained or remain in the solution.
[0246] Next, the hydrocarbyloxy group (OR 3 ) for explanation.
[0247] As R 3 The hydrocarbon group represented by is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, and more preferably an alkyl group or aryl group having 3 to 10 carbon atoms.
[0248] As R 3 , there are no particular limitations, for example, methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc.
[0249] Particularly more preferred are butyl, 1-methylpropyl, 2-methylpentyl and 2-ethylhexyl.
[0250] The method for synthesizing the organomagnesium compound (A-1) is not particularly limited, and examples thereof include the following method: 1 MgX 1 Japanese style: R 1 2Mg(R 1 As mentioned above, X 1 Any one of the organomagnesium compounds in the group consisting of halogen atoms) and belonging to the formula: M 1 R 2 k Japanese style: M 1 R 2 (k-1) H(M 1 , R 2 and k as described above) in an inert hydrocarbon solvent at a temperature of 25°C to 150°C, and then, if necessary, with a 2 (R 2 As described above) represented by a hydrocarbon alcohol or a hydrocarbon soluble in an inert hydrocarbon solvent having a 2 The organomagnesium compound (A-1) is synthesized by reacting a hydrocarbyl magnesium compound and / or a hydrocarbyl aluminum compound having a hydrocarbyl group represented by:
[0251] In the above method, when an organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an alcohol, the order of the reactions is not particularly limited, and any method of adding alcohol to the organomagnesium compound, adding the organomagnesium compound to alcohol, or adding both simultaneously can be used.
[0252] There is no particular restriction on the reaction ratio of the organic magnesium compound soluble in an inert hydrocarbon solvent and the alcohol, but as a result of the reaction, the molar composition ratio g / (γ+δ) of the hydrocarbon oxygen group in the obtained hydrocarbon oxygen group-containing organic magnesium compound relative to all metal atoms is 0≤g / (γ+δ)≤2, preferably 0≤g / (γ+δ)<1.
[0253] Next, the chlorinating agent (A-2) will be described.
[0254] The chlorinating agent (A-2) is a chlorinated silicon compound having at least one Si-H bond represented by (Formula ii).
[0255] (A-2): H h SiCl i R 4 (4-(h+i)) ……(Formula ii)
[0256] (In formula ii, R 4 is a hydrocarbon group having 1 or more and 12 or less carbon atoms, and h and i are real numbers satisfying the following relationship: 0<h, 0<i, 0<h+i≤4)
[0257] In the above (Formula ii), as R 4 The hydrocarbon group represented by is not particularly limited, and examples thereof include aliphatic hydrocarbon groups, alicyclic hydrocarbon groups and aromatic hydrocarbon groups. Specifically, examples thereof include methyl, ethyl, propyl, 1-methylethyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl.
[0258] Particularly preferred are alkyl groups having 1 to 10 carbon atoms, and more preferred are alkyl groups having 1 to 3 carbon atoms such as methyl, ethyl, propyl, and 1-methylethyl. In addition, h and i are numbers satisfying the relationship h+i≤4 and greater than 0, and i is preferably 2 to 3.
[0259] There are no particular limitations on the chlorinating agent (A-2), and examples thereof include HSiCl3, HSiCl2CH3, HSiCl2C2H5, HSiCl2(C3H7), HSiCl2(2-C3H7), HSiCl2(C4H9), HSiCl2(C6H5), HSiCl2(4-Cl-C6H4), HSiCl2(CH=CH2), HSiCl2(CH2C6H5), HSiCl2(1-C 10H7), HSiCl2(CH2CH=CH2), H2SiCl(CH3), H2SiCl(C2H5), HSiCl(CH3)2, HSiCl(C2H5)2, HSiCl(CH3)(2-C3H7), HSiCl(CH3)(C6H5), HSiCl(C6H5)2, etc.
[0260] As the chlorinating agent (A-2), a chlorinated silicon compound containing these compounds or a mixture of two or more selected from these compounds is used.
[0261] Particularly preferred are HSiCl3, HSiCl2CH3, HSiCl(CH3)2, and HSiCl2(C3H7), and more preferred are HSiCl3 and HSiCl2CH3.
[0262] Next, the reaction between the organomagnesium compound (A-1) and the chlorinating agent (A-2) is described.
[0263] During the reaction, the chlorinating agent (A-2) is preferably diluted in advance with an inert hydrocarbon solvent, a chlorinated hydrocarbon such as 1,2-dichloroethane, o-dichlorobenzene, dichloromethane, or an ether solvent such as diethyl ether or tetrahydrofuran, or a mixed solvent thereof. Among them, an inert hydrocarbon solvent is more preferably used in view of the performance of the catalyst.
[0264] The reaction ratio of the organomagnesium compound (A-1) and the chlorinating agent (A-2) is not particularly limited, but the number of moles of silicon atoms contained in (A-2) is preferably 0.01 mol or more and 100 mol or less, and more preferably 0.1 mol or more and 10 mol or less, relative to 1 mol of magnesium atoms contained in (A-1).
[0265] The reaction method of the organomagnesium compound (A-1) and the chlorinating agent (A-2) is not particularly limited, and any of the following methods can be used: a method in which (A-1) and (A-2) are simultaneously introduced into a reactor and reacted simultaneously; a method in which (A-2) is previously introduced into a reactor and then (A-1) is introduced into the reactor; or a method in which (A-1) is previously introduced into a reactor and then (A-2) is introduced into the reactor.
[0266] Particularly preferred is a method in which (A-2) is previously charged into a reactor and then (A-1) is introduced into the reactor.
[0267] The support (A-3) obtained by the above reaction is preferably separated by filtration or decantation, and then sufficiently washed with an inert hydrocarbon solvent to remove unreacted substances, by-products, and the like.
[0268] The reaction temperature of the organomagnesium compound (A-1) and the chlorinating agent (A-2) is not particularly limited, but is preferably 75° C. to 150° C., more preferably 80° C. to 120° C., and even more preferably 80° C. to 100° C. from the viewpoint of increasing the pores of the support (A-3) and making the support (A-3) easily ruptured.
[0269] In the simultaneous addition method of simultaneously introducing (A-1) and (A-2) into a reactor and reacting them, it is preferred to adjust the temperature of the reactor to a predetermined temperature in advance and adjust the temperature in the reactor to the predetermined temperature while performing the simultaneous addition.
[0270] In the method of charging (A-2) into a reactor in advance and then introducing (A-1) into the reactor, it is preferred that the temperature of the reactor into which the chlorinating agent (A-2) is charged is adjusted to a predetermined temperature, and the temperature in the reactor is adjusted to a predetermined temperature simultaneously with the introduction of the organomagnesium compound (A-1) into the reactor.
[0271] In a method in which (A-1) is previously charged into a reactor and then (A-2) is introduced into the reactor, it is preferred that the temperature of the reactor into which (A-1) has been charged is adjusted to a predetermined temperature, and the temperature in the reactor is adjusted to a predetermined temperature simultaneously with the introduction of (A-2) into the reactor.
[0272] The concentration of (A-1) (magnesium concentration) in the reaction system of the organomagnesium compound (A-1) and the chlorinating agent (A-2) is not particularly limited, but is preferably 0.8 mol / L or more and 2.5 mol / L or less, and more preferably 1.0 mol / L or more and 2.0 mol / L or less, from the viewpoint of increasing the pores of the support (A-3) and making the support (A-3) easily breakable.
[0273] Next, the organomagnesium compound (A-4) is described.
[0274] As (A-4), a compound represented by the aforementioned (Formula iii) is preferred.
[0275] (A-4): (M 2 ) α (Mg) β (R 4 ) a (R 5 ) b Y 1 c ……(Formula iii)
[0276] (In formula iii, M 2 is a metal atom belonging to any one selected from the group consisting of Group 12, Group 13 and Group 14 of the Periodic Table, R4 and R 5 is a hydrocarbon group having 2 or more and 20 or less carbon atoms, Y 1 is alkoxy, silyloxy, allyloxy, amino, amide, -N=CR 6 ,R 7 、-SR 8 (Here, R 6 , R 7 and R 8 represents a hydrocarbon group having 1 to 20 carbon atoms. When c is 2, Y 1 (may be different from each other) and any of the β-keto acid residues, α, β, a, b and c are real numbers satisfying the following relationship.
[0277] 0≤α, 0<β, 0≤a, 0≤b, 0≤c, 0<a+b, 0≤c / (α+β)≤2, nα+2β=a+b+c (here, n represents M 2 valence.
[0278] Regarding the amount of the organomagnesium compound (A-4) used, the molar ratio of the magnesium atoms contained in the organomagnesium compound (A-4) to the titanium atoms contained in the titanium compound (A-5) is preferably Mg / Ti=0.1 to 10, more preferably 0.5 to 5.
[0279] The reaction temperature of the organomagnesium compound (A-4) and the titanium compound (A-5) is not particularly limited, but is preferably -80°C to 150°C, and more preferably -40°C to 100°C.
[0280] The concentration of the organomagnesium compound (A-4) when used is not particularly limited, but is preferably 0.1 mol / L or more and 2 mol / L or less, and more preferably 0.5 mol / L or more and 1.5 mol / L or less, based on the magnesium atom contained in the organomagnesium compound (A-4). It should be noted that an inert hydrocarbon solvent is preferably used when diluting the organomagnesium compound (A-4).
[0281] Next, the titanium compound (A-5) is described.
[0282] As described above, the titanium compound (A-5) is a titanium compound represented by the following formula iv.
[0283] (A-5): Ti(OR 9 ) d X 1 (4-d) ……(Formula iv)
[0284] (In formula iv, d is a real number greater than or equal to 0 and less than or equal to 4, R 9is a hydrocarbon group having 1 to 20 carbon atoms, X 1 is a halogen atom.)
[0285] In the above (Formula iv), d is preferably 0 or more and 1 or less, and d is more preferably 0.
[0286] In (Formula iv), as R 9 The hydrocarbon group represented by is not particularly limited, and examples thereof include aliphatic hydrocarbon groups such as methyl, ethyl, propyl, butyl, pentyl, hexyl, 2-ethylhexyl, heptyl, octyl, decyl, and allyl; alicyclic hydrocarbon groups such as cyclohexyl, 2-methylcyclohexyl, and cyclopentyl; and aromatic hydrocarbon groups such as phenyl and naphthyl. Aliphatic hydrocarbon groups are particularly preferred.
[0287] As X 1 The halogen represented by is not particularly limited, and examples thereof include chlorine, bromine, and iodine, with chlorine being particularly preferred.
[0288] The titanium compound (A-5) may be used alone or in combination of two or more.
[0289] The amount of the titanium compound (A-5) used is not particularly limited, but from the viewpoint of increasing the amount supported in the pores of the carrier, the molar ratio of titanium to magnesium atoms contained in the carrier (A-3) (Ti / Mg) is preferably 0.15 to 20, more preferably 0.2 to 10.
[0290] The reaction temperature of the titanium compound (A-5) is not particularly limited, but is preferably -80°C to 150°C, and more preferably -40°C to 100°C.
[0291] There are no particular restrictions on the method for supporting the titanium compound (A-5) on the support (A-3), and a method of reacting an excess of the titanium compound (A-5) relative to the support (A-3) or a method of efficiently supporting the titanium compound (A-5) by using a third component can be used. A method in which the titanium compound (A-5) is supported on the support (A-3) by reacting it with an organomagnesium compound (A-4) is particularly preferred.
[0292] There is no particular restriction on the order of adding the organic magnesium compound (A-4) and the titanium compound (A-5) to the carrier (A-3), and any of the following methods may be used: adding the titanium compound (A-5) after adding the organic magnesium compound (A-4), adding the organic magnesium compound (A-4) after adding the titanium compound (A-5), or adding the organic magnesium compound (A-4) and the titanium compound (A-5) simultaneously.
[0293] In particular, a method of adding the organomagnesium compound (A-4) and the titanium compound (A-5) simultaneously is preferred.
[0294] The reaction of the organomagnesium compound (A-4) and the titanium compound (A-5) is carried out in an inert hydrocarbon solvent, preferably an aliphatic hydrocarbon solvent such as hexane or heptane.
[0295] The catalyst obtained as described above is used in the form of a slurry solution using an inert hydrocarbon solvent.
[0296] When the slurry solution is transported, it is preferred to add a thickener or to control so as to reduce the pressure difference between the transport source and the transport destination from the viewpoint of preventing the obtained catalyst from being broken before the polymerization step.
[0297] The thickener is not particularly limited, but from the viewpoint of maintaining the performance of the catalyst, saturated hydrocarbons are preferred, and specific examples thereof include liquid paraffin and polyolefin wax.
[0298] The pressure difference between the transport source and the transport destination is not particularly limited, but is preferably 0.1 MPa to 0.5 MPa, and more preferably 0.1 MPa to 0.3 MPa.
[0299] Next, the organometallic compound component [B] used as a catalyst component in the polymerization of the polyethylene powder according to the present embodiment will be described.
[0300] The catalyst used for polymerization of the polyethylene powder of the present embodiment is a highly active solid catalyst for polymerization by combining the solid catalyst component [A] and the organometallic compound component [B].
[0301] The organometallic compound component [B] is sometimes referred to as a "co-catalyst".
[0302] The organometallic compound component [B] is preferably a compound containing a metal belonging to any of the groups consisting of Group 1, Group 2, Group 12 and Group 13 of the periodic table, and is particularly preferably an organoaluminum compound and / or an organomagnesium compound.
[0303] As the organoaluminum compound, it is preferred to use a compound represented by the following (Formula v) alone or in combination.
[0304] AHr 10 j Z 1 (3-j) ……(Formula v)
[0305] (In formula v, R 10 is a hydrocarbon group having 1 to 20 carbon atoms, Z 1 is any group belonging to the group consisting of hydrogen, halogen, hydrocarbonoxy, allyloxy, and silyloxy, and j is a number of 2 to 3.
[0306] In the above formula v, 10 The hydrocarbon group having a carbon number of 1 or more and 20 or less is not particularly limited, and examples thereof include hydrocarbon groups including aliphatic hydrocarbon groups, aromatic hydrocarbon groups, or alicyclic hydrocarbon groups. Specifically, examples thereof include trialkylaluminum such as trimethylaluminum, triethylaluminum, tripropylaluminum, tributylaluminum, tri(2-methylpropyl)aluminum (or triisobutylaluminum), tripentylaluminum, tri(3-methylbutyl)aluminum, trihexylaluminum, trioctylaluminum, and tridecylaluminum; aluminum halide compounds such as diethylaluminum chloride, ethylaluminum dichloride, bis(2-methylpropyl)aluminum chloride, ethylaluminum sesquichloride, and diethylaluminum bromide; aluminum alkoxy compounds such as ethoxydiethylaluminum and butoxydi(2-methylpropyl)aluminum; aluminum siloxy compounds such as dimethylhydrogensiloxydimethylaluminum, ethylmethylhydrogensiloxydiethylaluminum, and ethyldimethylsiloxydiethylaluminum; and mixtures thereof as preferred substances.
[0307] In particular, trialkylaluminum compounds are more preferred.
[0308] As the organomagnesium compound, an organomagnesium compound soluble in an inert hydrocarbon solvent represented by the above-mentioned (Formula i) is preferred.
[0309] For γ, δ, e, f, g, M in the above (Formula i), 1 , R 1 , R 2 , OR 3 As described above, the organic magnesium compound preferably has high solubility in an inert hydrocarbon solvent, so β / α is preferably in the range of 0.5 to 10. In addition, M 1 Aluminum compounds.
[0310] There is no particular limitation on the method of adding the solid catalyst component [A] and the organometallic compound component [B] to the polymerization system under polymerization conditions. They may be added separately or reacted in advance before adding to the polymerization system.
[0311] The ratio of the two components in combination is not particularly limited, but the amount of the organometallic compound component [B] is preferably 1 mmol or more and 3000 mmol or less per 1 g of the solid catalyst component [A].
[0312] (Polymerization method of ethylene polymer)
[0313] Examples of a method for polymerizing the ethylene-based polymer constituting the polyethylene powder of the present embodiment include a method of polymerizing ethylene or copolymerizing ethylene and a comonomer by a suspension polymerization method or a gas phase polymerization method.
[0314] Among them, the suspension polymerization method is preferred because it can effectively remove the heat of polymerization.
[0315] In the suspension polymerization method, an inert hydrocarbon medium can be used as a solvent, and olefin itself can also be used as a solvent.
[0316] There are no particular restrictions on the inert hydrocarbon medium, and examples thereof include: aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, kerosene, etc.; alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc.; aromatic hydrocarbons such as benzene, toluene, xylene, etc.; halogenated hydrocarbons such as ethyl chloride, chlorobenzene, dichloromethane, etc.; or mixtures thereof, etc.
[0317] In the polymerization of ethylene polymers in the method for producing polyethylene powder of the present embodiment, there is no particular limitation on the method of adding the above-mentioned [catalyst component] into the polymerization reactor. However, from the viewpoint of obtaining a component having strongly entangled molecular chains by polymerization in the pores of the catalyst and from the viewpoint of making the catalyst easily breakable in the polymerization system, it is preferred to add a [catalyst component] that has been pre-polymerized.
[0318] The polymerization temperature of the ethylene polymer in the method for producing the polyethylene powder of the present embodiment is preferably 40°C to 100°C, more preferably 45°C to 95°C, and even more preferably 50°C to 90°C.
[0319] When the polymerization temperature is 40° C. or higher, industrially efficient production can be achieved. On the other hand, when the polymerization temperature is 100° C. or lower, block-like scale generated by partial melting of the polymer can be suppressed, and continuous and stable production can be achieved without clogging the pipeline.
[0320] The polymerization pressure of the ethylene polymer in the method for producing the polyethylene powder of the present embodiment is preferably normal pressure or higher and 2 MPaG or lower, more preferably 0.2 MPaG or higher and 1.5 MPaG or lower, and further preferably 0.3 MPaG or higher and 0.9 MPaG or lower.
[0321] When the polymerization pressure is at least normal pressure, industrially efficient production can be performed. On the other hand, when the polymerization pressure is 2 MPaG or less, there is a tendency that stable production can be performed without causing bulk fouling due to rapid polymerization in the polymerization reactor.
[0322] Generally, when obtaining an ethylene-based polymer by polymerization, an antistatic agent such as Stadis or STATSAFE manufactured by Innospec (whose agent is Maruwa Bussan Co., Ltd.) can be used to suppress static electricity adhesion of the polymer to the polymerization reactor.
[0323] For antistatic agents such as Stadis and STATSAFE, the antistatic agent diluted in an inert hydrocarbon medium can be added to the polymerization reactor using a pump, etc. The antistatic agent can be added by a method of adding it to a solid catalyst in advance, a method of adding it to the polymerization reactor, etc., and the amount of the antistatic agent added is preferably 1 ppm or more and 500 ppm or less, and more preferably 10 ppm or more and 100 ppm or less relative to the production of the ethylene polymer per unit time.
[0324] The molecular weight of the ethylene polymer can be adjusted by allowing hydrogen to exist in the polymerization system or by changing the polymerization temperature, as described in German Patent Application Publication No. 3127133.
[0325] Specifically, by adding hydrogen as chain transfer agent in the polymerization system, the molecular weight of ethylene polymer can be controlled within an appropriate range. When adding hydrogen in the polymerization system, as the scope of the mole fraction of hydrogen, preferably 0 mol % or more and 30 mol % or less, more preferably 0 mol % or more and 25 mol % or less.
[0326] In addition, hydrogen can also be contacted with the catalyst in advance and then added to the polymerization system from the catalyst introduction line. Just after the catalyst is introduced into the polymerization system, the catalyst concentration near the introduction line outlet becomes high, so rapid polymerization is performed, and the possibility of generating a local high temperature state increases. On the other hand, by contacting hydrogen with the catalyst before being introduced into the polymerization system, the initial activity of the catalyst can be suppressed, and the generation of block fouling caused by rapid polymerization, the deactivation of the catalyst at high temperature, etc. can be suppressed.
[0327] The concentration range of the polymerization slurry in the method for producing the ethylene-based polymer constituting the polyethylene powder of the present embodiment is preferably 30% by mass or more and 60% by mass or less, and more preferably 40% by mass or more and 50% by mass or less, from the viewpoint that the catalyst is easily broken in the polymerization system.
[0328] The stirring speed in the method for producing the ethylene-based polymer constituting the polyethylene powder of the present embodiment is preferably in the range of 300 rpm to 600 rpm, more preferably in the range of 400 rpm to 500 rpm, from the viewpoint that the catalyst is easily broken in the polymerization system.
[0329] The polymerization reaction may be carried out in any of a batch mode, a semi-continuous mode or a continuous mode, but is preferably carried out in a continuous mode.
[0330] By continuously supplying ethylene gas, solvent, catalyst, etc. into the polymerization system, and continuously discharging together with the generated ethylene polymer, the local high temperature state caused by the rapid ethylene reaction can be suppressed, and the polymerization system becomes more stable. When ethylene reacts in a uniform state in the system, it is possible to suppress the generation of side chains, double bonds, etc. in the polymer chain, or it is possible to suppress the generation of low molecular weight components and ultra-high molecular weight bodies due to the decomposition and crosslinking of the ethylene polymer, and it is easy to generate the crystalline components of the ethylene polymer. Thus, in the film, microporous membrane, etc. of the polyethylene powder used in the present embodiment, it is easy to obtain a sufficient amount of crystalline components required for strength.
[0331] The polymerization reaction may be a single-stage polymerization method using one polymerization reactor, or a multi-stage polymerization method in which polymerization is performed sequentially and continuously in two or more polymerization reactors connected in series.
[0332] Specifically, the production of the ethylene-based polymer using the multi-stage polymerization method is carried out by the method shown below.
[0333] First, an ethylene polymer X is produced in a first-stage polymerization reactor under the above-mentioned production conditions, and the ethylene polymer X extracted from the first-stage polymerization reactor is transferred to an intermediate flash tank to separate unreacted ethylene, hydrogen, and comonomer (limited to the case where copolymerization is performed in the first-stage polymerization reactor). Then, a suspension containing the ethylene polymer X is transferred to a second-stage polymerization reactor, and an ethylene polymer Y is produced under the above-mentioned production conditions.
[0334] The range of the polymerization pressure in the first-stage polymerization reactor is preferably 0.6 MPaG to 2.0 MPaG, more preferably 0.7 MPaG to 1.5 MPaG, and even more preferably 0.8 MPaG to 1.0 MPaG, from the viewpoint of obtaining components with strong entanglement of molecular chains by polymerization in the pores of the catalyst.
[0335] The concentration range of the polymerization slurry in the first-stage polymerization reactor is preferably 10% by mass or more and 30% by mass or less, and more preferably 10% by mass or more and 20% by mass or less, from the viewpoint of controlling so that the catalyst is not broken in the first-stage polymerization reactor.
[0336] The stirring speed in the first-stage polymerization reactor is preferably in the range of 100 rpm to 300 rpm, and more preferably in the range of 150 rpm to 250 rpm, from the viewpoint of controlling so that the catalyst is not broken in the first-stage polymerization reactor.
[0337] The concentration range of the polymerization slurry in the second-stage polymerization reactor is preferably 30% by mass or more and 60% by mass or less, and more preferably 40% by mass or more and 50% by mass or less, from the viewpoint of making the catalyst easily break in the polymerization system.
[0338] The stirring speed in the polymerization reactor of the second stage is preferably in the range of 300 rpm to 600 rpm, and more preferably in the range of 400 rpm to 500 rpm, from the viewpoint of making the catalyst easily break in the polymerization system.
[0339] The ratio of the ethylene polymer X contained in the polyethylene powder produced by the multi-stage polymerization method, that is, the range of the production amount in the polymerization reactor of the first stage, is preferably 10 mass % or more and 50 mass % or less, more preferably 15 mass % or more and 45 mass % or less, and still more preferably 20 mass % or more and 40 mass % or less, from the viewpoint of controlling the catalyst to break in the polymerization reactor of the second stage.
[0340] As various physical property values of the ethylene polymer Y, the above-mentioned viscosity average molecular weight and density can be obtained by measuring the physical property values of the ethylene polymer X extracted from the first-stage polymerization reactor and the finally produced polyethylene powder, and then calculating the physical property values based on the production amounts in each polymerization reactor according to additivity.
[0341] A suspension containing an ethylene-based polymer constituting the polyethylene powder of this embodiment is quantitatively extracted from a polymerization reactor and transferred to a flash tank to separate unreacted ethylene, hydrogen, and comonomer (only when copolymerization is carried out in a reactor).
[0342] The solvent separation method in the polymerization step of the polyethylene powder of the present embodiment can be any of decantation, centrifugation, filtration, etc., and centrifugation is more preferred because it has a good separation efficiency between the ethylene polymer and the solvent.
[0343] The method for deactivating the catalyst used in the polymerization step of the ethylene polymer constituting the polyethylene powder of the present embodiment is not particularly limited, but the deactivation of the catalyst is preferably carried out after the ethylene polymer and the solvent are separated.
[0344] By introducing a reagent for deactivating the catalyst after separating the polyethylene powder from the solvent, it is possible to suppress precipitation of low molecular weight components, catalyst components, etc. contained in the solvent into the ethylene-based polymer.
[0345] Examples of the agent for deactivating the catalyst include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, and alkynes.
[0346] In the method for producing polyethylene powder of the present embodiment, it is preferred that a drying step is performed after the ethylene polymer is separated from the solvent. In the drying step, a rotary kiln method, a paddle method, a fluidized bed dryer, etc. are preferably used. In addition, the drying temperature is preferably 50° C. or higher and 150° C. or lower, and more preferably 70° C. or higher and 110° C. or lower.
[0347] In addition, it is also effective to introduce an inert gas such as nitrogen into the dryer to promote drying. In this case, a method of adding steam or the like as a reagent for deactivating the catalyst is also more effective.
[0348] After drying the ethylene-based polymer constituting the polyethylene powder of the present embodiment, the ethylene-based polymer may be sieved to remove coarse powder.
[0349] The polyethylene powder of the present embodiment may be a mixture of a plurality of polyethylene powders containing an ethylene-based polymer obtained by the above-mentioned production method.
[0350] Furthermore, the present invention may be used in combination with known additives such as a slip agent, a neutralizer, an antioxidant, a light stabilizer, an antistatic agent, and a pigment, as required.
[0351] The lubricant or neutralizer is not particularly limited, and examples thereof include aliphatic hydrocarbons, higher fatty acids, higher fatty acid metal salts, alcohol fatty acid esters, waxes, higher fatty acid amides, silicone oils, rosin, etc. Specifically, stearates such as calcium stearate, magnesium stearate, and zinc stearate can be cited as appropriate additives.
[0352] The antioxidant is not particularly limited, but for example, phenolic compounds or phenolic phosphorus-containing compounds are preferred. Specifically, phenolic antioxidants such as 2,6-di-tert-butyl-4-methylphenol (butylhydroxytoluene), octadecyl 3-(4-hydroxy-3,5-di-tert-butylphenyl) propionate, and tetrakis(methylene(3,5-di-tert-butyl-4-hydroxyhydrocinnamate))methane; phenolic phosphorus-containing antioxidants such as 6-[3-(3-tert-butyl-4-hydroxy-5-methylphenyl)propoxy]-2,4,8,10-tetra-tert-butyldibenzo[d,f][1,3,2]dioxaphosphophetidine; and phosphorus-containing antioxidants such as 4,4'-biphenylene diphosphite tetrakis(2,4-di-tert-butylphenyl) ester, tris(2,4-di-tert-butylphenyl) phosphite, and cyclic neopentanetetraylbis(2,4-di-tert-butylphenyl phosphite).
[0353] The light stabilizer is not particularly limited, and examples thereof include benzotriazole-based light stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-tert-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based light stabilizers such as bis(2,2,6,6-tetramethyl-4-piperidinyl) sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidinyl)imino)hexamethylene}{(2,2,6,6-tetramethyl-4-piperidinyl)imino}].
[0354] The antistatic agent is not particularly limited, and examples thereof include aluminosilicate, kaolin, clay, natural silica, synthetic silica, silicates, talc, diatomaceous earth, and fatty acid glycerides.
[0355] [use]
[0356] The polyethylene powder of the present embodiment can be used as a raw material for various molded bodies such as microporous films, fibers, particularly high-strength fibers, sintered bodies, press-molded bodies, and plunger extrusion-molded bodies.
[0357] It is particularly suitable as a raw material for microporous membranes used in battery separators.
[0358] [Molding body]
[0359] The molded product of the present embodiment is a molded product of the polyethylene powder of the present embodiment described above.
[0360] Examples of the molded product include microporous films, particularly microporous films used as battery separators, fibers, particularly high-strength fibers, sintered bodies, press-molded bodies, and plunger extrusion-molded bodies.
[0361] As a method for producing a molded body, there can be mentioned a molding method which involves the steps of extrusion of a resin using a wet extrusion method, stretching, extraction, and drying.
[0362] Examples of the battery separator include a lithium ion secondary battery separator and a lead acid battery separator.
[0363] Example
[0364] Hereinafter, the present embodiment will be described in more detail by way of specific examples and comparative examples, but the present invention is not limited to the following examples and comparative examples.
[0365] First, the method for evaluating the physical properties of polyethylene powder will be described.
[0366] [Physical properties of polyethylene powder]
[0367] (Ratio of components with intermediate entanglement index and mobility at 180°C)
[0368] First, a sample tube filled with polyethylene powder to a height of 1 cm from the bottom was placed in a TD-NMR apparatus (model: minispec mq20) manufactured by Bruker set to an internal temperature of 30°C, and the sample tube was heated according to the <temperature increase conditions> shown below.
[0369] The temperature shown in the following <Temperature Increase Conditions> is a value obtained by measuring the internal temperature of the sample using a thermocouple.
[0370] <Temperature rising conditions>
[0371] (1) Set to 30°C and let stand for 5 minutes.
[0372] (2) Raise the temperature to 180°C at a rate of 5°C / min.
[0373] (3) After heating to 180°C, let stand for 25 minutes.
[0374] After the temperature increase is completed according to the above steps, the spin-spin relaxation time (T2, sometimes simply referred to as "relaxation time" in this specification) of the sample is measured under the <measurement conditions> shown below.
[0375] Then, after the measurement was completed, the same measurement was repeated three times, for a total of four measurements.
[0376] <Measurement conditions>
[0377] Magnetic field strength: 0.47T
[0378] Determination of nuclear types: 1 H(20MHz)
[0379] Determination method: Carr Purcell Meiboom Gill method
[0380] Cumulative times: 256 times
[0381] Repeat time: 3 seconds
[0382] The interval between the first 90° pulse and the 180° pulse (τ): 0.04 ms
[0383] Total echo signal number: 6400
[0384] The free induction decay (FID) obtained by the fourth measurement among all the four measurements was subjected to curve fitting using the analysis program TD-NMR-A manufactured by Bruker.
[0385] The function shown in the following <Formula 1> was used for fitting.
[0386] <Formula 1>
[0387] f(t)=R α exp(-t / T α )+R β exp(-t / T β )+R γ exp(-t / T γ )
[0388] (Among them, R α +R β +R γ =100)
[0389] t: variable (elapsed time from the start of pulse radiation)
[0390] T α : Relaxation time of the low-mobility component α (milliseconds)
[0391] R α : Existence ratio of component α with low motility (%)
[0392] T β : relaxation time of the component β with medium mobility (milliseconds)
[0393] R β : Existence ratio of component β with intermediate motility (%)
[0394] T γ : Relaxation time of the highly mobile component γ (milliseconds)
[0395] R γ : Existence ratio of component γ with high mobility (%)
[0396] Finally, based on the relaxation time T and the existence ratio R obtained by curve fitting of the free induction decay, the entanglement index (milliseconds) and the motility-centered component ratio were calculated according to (Formula I) and (Formula II) shown below.
[0397] (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )......(Formula I)
[0398] (Ratio of components with medium mobility) = R β / (R α +Rβ )……(Formula II)
[0399] (Rate of change in abundance ratio of components with low mobility at 180°C)
[0400] The free induction decay (FID) obtained by the first and fourth measurements in the pulse NMR measurement when determining the above (entanglement index at 180° C. and the ratio of components with intermediate mobility) was curve-fitted using the analysis program TD-NMR-A manufactured by Bruker.
[0401] The function shown in the above <Formula 1> was used for fitting.
[0402] From the abundance ratio R obtained by fitting, the change rate (%) of the abundance ratio of the component with low mobility is calculated according to the following (Formula III).
[0403] (Rate of change in abundance ratio of components with low mobility) = ((R α4 -R α1 ) / R α1 )×100……(Formula III)
[0404] R α1 : Existence ratio of component α with low motility in the first measurement (%)
[0405] R α4 : Existence ratio of component α with low motility at the fourth measurement (%)
[0406] (Change rate of the abundance ratio of components with high mobility at 180°C)
[0407] The free induction decay (FID) obtained by the first and fourth measurements in the pulse NMR measurement when determining the above (entanglement index at 180° C. and the ratio of components with intermediate mobility) was curve-fitted using the analysis program TD-NMR-A manufactured by Bruker.
[0408] The function shown in the above <Formula 1> is used for fitting.
[0409] From the abundance ratio R obtained by fitting, the change rate (%) of the abundance ratio of the component with high mobility is calculated according to the (Formula IV) shown below.
[0410] (Ratio of change in abundance of components with high mobility) = ((R γ4 -R γ1 ) / R γ1 )×100……(Formula IV)
[0411] R γ1: Existence ratio of component γ with high mobility in the first measurement (%)
[0412] R γ4 : Existence ratio of component γ with high mobility in the fourth measurement (%)
[0413] [Isothermal crystallization time]
[0414] The isothermal crystallization time of the polyethylene powder at 125° C. was determined by the following method using a differential scanning calorimeter (manufactured by PerkinElmer Inc. / product name: DSC8000).
[0415] First, an aluminum pan containing 8.5 mg of polyethylene powder was placed in a heating furnace in a DSC apparatus, and a heating operation was performed according to the <temperature increase and decrease conditions> shown below.
[0416] Among them, all heating operations were carried out under a nitrogen atmosphere.
[0417] <Temperature rise and fall conditions>
[0418] (1) Maintain at 50°C for 1 minute.
[0419] (2) Raise the temperature to 180°C at a rate of 200°C / min.
[0420] (3) Maintain at 180°C for 5 minutes.
[0421] (4) Cool down to 125°C at a rate of 80°C / min.
[0422] Then, the time when the temperature reaches 125° C. is defined as the starting point (0 minute), and the time when the peak top of the exothermic peak due to crystallization is obtained is defined as the isothermal crystallization time (minutes) at 125° C.
[0423] (Viscosity average molecular weight (Mv))
[0424] The viscosity average molecular weight of the polyethylene powder is measured by the method shown below in accordance with ISO 1628-3 (2010).
[0425] First, polyethylene powder in the range of 4.0 mg to 4.5 mg was weighed in a dissolving tube. The weighed mass was recorded as "m (unit: mg)" in the following formula. Next, the air inside the dissolving tube was exhausted by a vacuum pump and replaced with nitrogen, and then 20 mL of decalin (1 g / L of 2,6-di-tert-butyl-4-methylphenol, hereinafter referred to as decalin, was added after degassing by a vacuum pump and replacing with nitrogen, and the polyethylene powder was dissolved by stirring at 150°C for 90 minutes to prepare a decalin solution.
[0426] Then, the decalin solution was placed in a Cannon-Fenske viscometer (manufactured by Shibata Scientific Instruments Co., Ltd. / viscometer No. 100) in a constant temperature liquid bath at 135° C., and the falling time (ts) between the marked lines was measured.
[0427] In addition, the falling time (tb) of decalin alone without adding polyethylene powder was measured as a blank, and the specific viscosity (ηsp) was calculated according to the following (Formula A).
[0428] ηsp=(ts / tb)-1(Formula A)
[0429] The intrinsic viscosity IV was calculated from the specific viscosity (ηsp) and the concentration (C) (unit: g / dL) using the following (Formula B) and (Formula C).
[0430] Concentration C = m / (20×γ) / 10 (unit: g / dL) (Formula B)
[0431] γ = (density of decalin at 20°C) / (density of decalin at 135°C)
[0432] =0.888 / 0.802=1.107
[0433] Intrinsic viscosity IV = (ηsp / C) / (1+0.27×ηsp) (Formula C)
[0434] The intrinsic viscosity IV is substituted into the following (Formula D) to determine the viscosity average molecular weight (Mv).
[0435] Viscosity average molecular weight (Mv) = (5.34 × 10 4 )×[η] 1.49 (Formula D)
[0436] (Median particle size)
[0437] The median particle size of the polyethylene powder was determined by the method shown below.
[0438] The polyethylene powder was classified using a sieve according to the JIS Z8801 standard. The mass of the polyethylene powder recovered in each fraction was measured using sieves with mesh sizes of 425 μm, 300 μm, 212 μm, 150 μm, 106 μm, 75 μm and 53 μm. Then, the fraction (mass %) of each fraction relative to the total mass of the polyethylene powder before classification was calculated, and the cumulative undersize ratio (mass %) was calculated. A cumulative undersize distribution graph with the mesh size as the horizontal axis and the cumulative undersize ratio as the vertical axis, i.e., a cumulative particle size distribution curve (cumulative curve from small particles), was drawn, and the particle size (D50 (μm)) when the cumulative undersize ratio was 50% was taken as the median particle size.
[0439] [Method for producing microporous membrane]
[0440] 1 part by mass of pentaerythritol-tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant was added to 25 to 50 parts by mass of polyethylene powder of each of Examples and Comparative Examples described below, and dry-blended using a drum mixer to obtain a powder mixture.
[0441] The obtained powder mixture was replaced with nitrogen and then fed into a twin-screw extruder through a feeder under a nitrogen atmosphere.
[0442] Then, liquid paraffin (MORESCO Co., Ltd., P-350P (product name)) measured in such a way that the total amount with the polyethylene powder is 100 parts by mass is injected into a twin-screw extruder in a side-feed manner, kneaded at 200°C, extruded from a T-die disposed at the front end of the extruder, and then immediately cooled and solidified by a casting roll cooled to 25°C, thereby forming a gel-like sheet with a thickness of 1200 μm. The gel-like sheet was stretched to 7×7 times at 115°C to 125°C using a synchronous biaxial stretching machine to obtain a stretched film. Then, the stretched film was immersed in methyl ethyl ketone for 30 minutes to extract and remove the liquid paraffin, and then dried. Then, it was heat-set at 115°C to 125°C for 3 minutes to obtain a microporous membrane.
[0443] The stretching temperature and the heat setting temperature are appropriately adjusted for each microporous membrane within a specified temperature range.
[0444] [Evaluation of microporous membrane]
[0445] (Evaluation of Formability of Microporous Film)
[0446] As an evaluation index of molding processability, the uniformity of the thickness of the microporous membrane was evaluated.
[0447] Specifically, for the microporous membrane obtained by the above-mentioned [Microporous membrane production method], 8 films of 100 mm×50 mm were punched out from 250 mm×250 mm, and the film thickness of each film was measured at 23°C using a micro thickness gauge (model: KBM) manufactured by Toyo Seiki Seisaku-sho, Ltd.
[0448] The film thickness was measured at three locations on one punched film.
[0449] Then, the standard deviation of the measured values at a total of 24 points was calculated, and the moldability was evaluated based on the following evaluation criteria.
[0450] (Evaluation Criteria)
[0451] ◎(Good): Less than 0.5μm
[0452] ○(Normal): 0.5μm or more and less than 1μm
[0453] ×(bad): 1μm or more
[0454] (Evaluation of Mechanical Strength of Microporous Membrane)
[0455] As an evaluation index of mechanical strength, the puncture strength of the microporous membrane was evaluated.
[0456] Specifically, for the microporous membrane obtained by the above-mentioned [Method for producing microporous membrane], 8 sheets of 100 mm × 50 mm were punched out from 250 mm × 250 mm, and the puncture strength of each membrane was measured using a compression tester (model: KES-G5) manufactured by Kato Tech Co., Ltd. under the conditions of a curvature radius of the needle tip of 0.5 mm, a puncture speed of 2 mm / second, and 23° C. The measurement was performed at 3 locations on one punched membrane.
[0457] In addition, the mass of each punched film was measured to obtain the basis weight (per 1m 2 The puncture strength converted to basis weight is calculated by the following formula:
[0458] Then, the average value of the measured values at a total of 24 points was calculated, and the mechanical strength was evaluated according to the following evaluation criteria.
[0459] (Puncture strength calculated based on basis weight) = (Puncture strength [N]) / (Basis weight [g / m 2 ])
[0460] (Evaluation Criteria)
[0461] ◎(Good): 0.85N / (g / m 2 )above
[0462] ○(Normal): greater than or equal to 0.7N / (g / m 2 ) and less than 0.85N / (g / m 2 )
[0463] ×(Bad): less than 0.7N / (g / m 2 )
[0464] (Evaluation of Dimensional Stability of Microporous Membranes)
[0465] As an evaluation index of dimensional stability, the heat shrinkage of the microporous film was evaluated.
[0466] Specifically, eight films of 100 mm×50 mm were punched out from a 250 mm×250 mm microporous membrane obtained by the above-mentioned [Microporous membrane production method], and the films were left to stand in an oven set at 120° C. for 60 minutes.
[0467] After being heated and allowed to stand, the film was cooled at room temperature for 15 minutes, and then the size of the microporous film was measured and the heat shrinkage (%) was calculated by the following formula.
[0468] Then, the average value of the measured values at a total of 8 points was calculated, and the dimensional stability was evaluated according to the following evaluation criteria.
[0469] (Heat shrinkage ratio) = (Heat shrinkage ratio in MD direction) + (Heat shrinkage ratio in TD direction)
[0470] (Heat shrinkage in MD direction) = (1-D MD120 / D MD23 )×100
[0471] (Heat shrinkage in TD direction) = (1-D TD120 / D TD23 )×100
[0472] D MD120 :Dimensions in MD direction at 120°C [mm]
[0473] D MD23 :Dimensions in MD direction at 23°C [mm]
[0474] D TD120 :Dimensions in TD direction at 120°C [mm]
[0475] D TD23 :Dimensions in TD direction at 23°C [mm]
[0476] (Evaluation Criteria)
[0477] ◎(Good): Less than 15%
[0478] ○(Normal): 15% or more and less than 25%
[0479] × (poor): 25% or more
[0480] (Evaluation of creep resistance of microporous membrane)
[0481] A sample of 20 mm in width and 100 mm in length was cut out from the microporous membrane obtained by the above-mentioned [Method for producing microporous membrane] and installed in Tensilon manufactured by A&D Co., Ltd. with the chuck distance set to 50 mm. The sample was kept at a temperature of 23° C. and a load of 10 N for 12 hours, and then the length of the microporous membrane was measured, and the tensile elongation (%) was calculated by the following formula.
[0482] Then, creep resistance was evaluated according to the following evaluation criteria.
[0483] (tensile elongation) = {(L 12h / 100)-1}×100
[0484] L 12h : Length of microporous membrane after 12 hours [mm]
[0485] (Evaluation Criteria)
[0486] ◎(Good): Less than 5%
[0487] ○(Normal): 5% or more and less than 10%
[0488] × (difference): 10% or more
[0489] [Preparation of Ziegler-Natta Catalyst]
[0490] (Preparation of Ziegler-Natta Catalyst (A))
[0491] <(1) Synthesis of raw material (a-1)>
[0492] 2.5 mol / L of Mg6(C4H9) was added to an 8L stainless steel autoclave that had been fully purged with nitrogen. 12 800 mL of Al(C2H5)3 hexane solution (equivalent to 2000 mmol in total of magnesium and aluminum) was added dropwise with 146 mL of 5.47 mol / L n-butanol hexane solution over 3 hours while stirring at 50°C. After completion, the pipeline was cleaned with 200 mL of hexane. Then, stirring was continued at 50°C for 2 hours to allow the reaction to proceed.
[0493] After the reaction was completed, the product cooled to room temperature was used as the raw material (a-1). The raw material (a-1) had a magnesium concentration of 1.5 mol / L.
[0494] <(2) Synthesis of raw material (a-2)>
[0495] 1 mol / L of Mg6(C4H9) was added to an 8L stainless steel autoclave that had been fully purged with nitrogen. 12 2,000 mL of a hexane solution of Al(C2H5)3 (equivalent to 2,000 mmol in total of magnesium and aluminum) was stirred at 80°C, while 240 mL of a hexane solution of 8.33 mol / L methylhydrogenpolysiloxane (manufactured by Shin-Etsu Chemical Co., Ltd.) was pressure-fed, and stirring was continued at 80°C for 2 hours.
[0496] After the reaction is completed, the product cooled to room temperature is used as the raw material (a-2).
[0497] The total concentration of magnesium and aluminum in the raw material (a-2) was 0.786 mol / L.
[0498] <(3) Synthesis of carrier (a-3)>
[0499] 333 mL of a 3 mol / L hexane solution of hydroxytrichlorosilane was placed in an 8 L stainless steel autoclave that had been fully purged with nitrogen, and 629 mL of a hexane solution of the organic magnesium compound of the raw material (a-1) (equivalent to 943 mmol of magnesium) was added dropwise at 80°C over 3 hours, and then the reaction was continued while stirring at 80°C for 1 hour.
[0500] After the reaction was completed, the supernatant was removed and washed four times with 1,800 mL of hexane to obtain a carrier (a-3).
[0501] The carrier was analyzed and found to contain 7.5 mmol of magnesium per 1 g of solid.
[0502] <(4) Preparation of Ziegler-Natta Catalyst (A)>
[0503] In an 8 L stainless steel autoclave that had been fully purged with nitrogen, while stirring 1,970 mL of a hexane slurry containing 110 g of the support (a-3) at 10°C, 103 mL of a 1 mol / L hexane solution of titanium tetrachloride and 131 mL of the raw material (a-2) were added simultaneously over 3 hours.
[0504] After the addition, the reaction was continued for 1 hour at 10° C. After the reaction was completed, the supernatant was removed, and the unreacted raw material components were removed by washing with hexane 4 times, and then 10% by volume (volume ratio: liquid paraffin / (liquid paraffin+hexane)) of liquid paraffin (MORESCO Co., Ltd., P-350P (product name)) as a thickener was added to prepare a Ziegler-Natta catalyst (A).
[0505] When the Ziegler-Natta catalyst (A) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.3 MPa.
[0506] (Preparation of Ziegler-Natta Catalyst (B))
[0507] A 1.6L autoclave was used to prepolymerize 20g of the above-mentioned Ziegler-Natta catalyst (A). 800mL of n-hexane was used as a solvent, 0.4 mmol of triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) was used as a co-catalyst, and 20 mol% (molar ratio: hydrogen / (ethylene+hydrogen)) of hydrogen was supplied. The polymerization temperature was set to 20°C, and ethylene was supplied in such a manner that 5g of polyethylene was obtained for every 1g of Ziegler-Natta catalyst (A) polymerized. After the polymerization was completed, the supernatant was removed, and the unreacted raw material components were removed by washing with hexane 4 times, thereby preparing a Ziegler-Natta catalyst (B). When transporting the Ziegler-Natta catalyst (B), the pressure difference between the transport source and the transport destination was adjusted to 0.8MPa.
[0508] (Preparation of Ziegler-Natta Catalyst (C))
[0509] <(5) Synthesis of carrier (c-3)>
[0510] A support (c-3) was obtained by the same operation as in the synthesis of the support (a-3) except that the reaction temperature was set to 65° C. The support (c-3) was analyzed to find that the magnesium content per 1 g of the solid was 7.5 mmol.
[0511] <(6) Preparation of Ziegler-Natta Catalyst (C)>
[0512] The same operation as that for the preparation of the Ziegler-Natta catalyst (A) was performed except that the carrier (c-3) was used instead of the carrier (a-3) and liquid paraffin was not added, thereby preparing the Ziegler-Natta catalyst (C). When the Ziegler-Natta catalyst (C) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.3 MPa.
[0513] (Preparation of Ziegler-Natta Catalyst (D))
[0514] <(7) Synthesis of raw material (d-1)>
[0515] Use 2000mL of 1 mol / L Mg6(C4H9) 12 Al(C2H5)3 hexane solution was added, and the amount of n-hexane used for cleaning the pipeline was adjusted to 300 mL. In addition, the same operation as the synthesis of the above-mentioned raw material (a-1) was performed to obtain the raw material (d-1). The raw material (d-1) had a magnesium concentration of 0.7 mol / L.
[0516] <(8) Synthesis of carrier (d-3)>
[0517] The same operation as the synthesis of the above-mentioned carrier (a-3) was performed except that 1340 mL of the raw material (d-1) was used instead of 629 mL of the above-mentioned raw material (a-1) and the reaction temperature was set to 65° C., thereby obtaining the carrier (d-3). The carrier (d-3) was analyzed, and the result showed that the magnesium contained in 1 g of the solid was 7.5 mmol.
[0518] <(9) Preparation of Ziegler-Natta Catalyst (D)>
[0519] The same operation as that for the preparation of the Ziegler-Natta catalyst (A) was performed except that the carrier (d-3) was used instead of the carrier (a-3) and liquid paraffin was not added, thereby preparing a Ziegler-Natta catalyst (D). When the Ziegler-Natta catalyst (D) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.8 MPa.
[0520] (Preparation of Ziegler-Natta Catalyst (E))
[0521] Ziegler-Natta catalyst (E) was prepared by performing the same polymerization operation as that for preparing Ziegler-Natta catalyst (B) except that Ziegler-Natta catalyst (D) was used instead of Ziegler-Natta catalyst (A). When the Ziegler-Natta catalyst (E) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.3 MPa.
[0522] (Preparation of Ziegler-Natta Catalyst (F))
[0523] In an 8 L stainless steel autoclave fully purged with nitrogen, while stirring 1600 mL of hexane at 5°C, 786 mL of a 1 mol / L hexane solution of titanium tetrachloride and 1000 mL of the raw material (a-2) were added simultaneously over 4 hours.
[0524] After the addition, the temperature was slowly raised and the reaction was continued at 10°C for 1 hour.
[0525] After the reaction was completed, the supernatant was removed, and the unreacted raw material components were removed by washing with hexane four times, thereby preparing a Ziegler-Natta catalyst (F).
[0526] When the Ziegler-Natta catalyst (F) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.8 MPa.
[0527] (Preparation of Ziegler-Natta Catalyst (G))
[0528] 10 vol% (volume ratio: liquid paraffin / (liquid paraffin+hexane)) of liquid paraffin (MORESCO Co., Ltd., P-350P (product name)) as a thickener was added to the above-mentioned Ziegler-Natta catalyst (F) to prepare a Ziegler-Natta catalyst (G).
[0529] When the Ziegler-Natta catalyst (G) was transported, the pressure difference between the transport source and the transport destination was adjusted to 0.8 MPa.
[0530] [Manufacturing of polyethylene powder and microporous membrane]
[0531] (Example 1)
[0532] As described below, in the first stage polymerization reactor, the ethylene polymer (X A ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y A ), thereby obtaining polyethylene powder (A).
[0533] The polyethylene powder (A) had a viscosity average molecular weight of 300,000 and a median particle size of 101 μm.
[0534] Table 1 shows the results of the various evaluations performed on the polyethylene powder (A) and the microporous membrane of the polyethylene powder (A) produced by the above-mentioned [Method for producing microporous membrane].
[0535] <(1) Ethylene polymer (X A ) >
[0536] The polymerization of ethylene polymers was carried out using a container-type 300L polymerization reactor with a stirring blade with 3 retreating blades and 3 baffles. N-hexane as a solvent was supplied at a flow rate of 40L / hour, the total liquid volume was adjusted so that the slurry concentration was 16% by mass, and the stirring speed was set to 200rpm. Ziegler-Natta catalyst (A) was used as a polymerization catalyst, and was supplied in a manner such that the production rate of ethylene polymers was 9.0kg / hour. In the polymerization catalyst, STATSAFE3000 (90g / L) diluted with n-hexane was added in an amount of 20 mass ppm relative to the production rate of ethylene polymers. Triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) were used as co-catalyst components and supplied at 10 mmol / hour. 26 mol% (molar ratio: hydrogen / (ethylene+hydrogen)) of hydrogen was supplied. The polymerization temperature was set to 60°C, the polymerization pressure was set to 0.7MPaG, and the average residence time was set to 3.3 hours.
[0537] The ethylene polymer (X) obtained in this way A ) had a viscosity average molecular weight of 300,000. The polymerization activity in the first-stage polymerization reactor was 12,000 g per 1 g of the catalyst.
[0538] The polymerization slurry in the polymerization reactor was introduced into an intermediate flash tank at a pressure of 0.05 MPaG and a temperature of 70° C. in such a manner that the liquid level in the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated in the intermediate flash tank.
[0539] <(2) Ethylene polymer (Y A ) >
[0540] The ethylene polymer (X A ) was transferred from the intermediate flash tank to a 300L container-type polymerization reactor equipped with a stirring blade with three backward blades and three baffles, and then the ethylene polymer (Y A )’s aggregation.
[0541] The total liquid volume was adjusted so that the slurry concentration was 40% by mass, the stirring speed was set to 450 rpm, and triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) as co-catalyst components were supplied at 10 mmol / hour. Hydrogen was supplied at 10 mol% (molar ratio: hydrogen / (ethylene+hydrogen)). The polymerization temperature was set to 78°C, the polymerization pressure was set to 0.75 MPaG so that the production rate was 11.1 kg / hour, and the average residence time was set to 0.75 hours.
[0542] The ethylene polymer (Y A ) had a viscosity average molecular weight of 300,000. The polymerization activity in the second-stage polymerization reactor was 14,700 g per 1 g of the catalyst.
[0543] The polymerization slurry in the polymerization reactor was introduced into a final flash tank at a pressure of 0.05 MPaG and a temperature of 70° C. in such a manner that the liquid level in the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated in the final flash tank. Next, the polymerization slurry was continuously sent from the flash tank to a centrifuge by a pump, and the polymer and the solvent were separated in the centrifuge. The separated polyethylene powder was then sent to a rotary kiln type dryer controlled at 90° C. and dried while blowing nitrogen, thereby obtaining polyethylene powder (A). It should be noted that in this drying step, steam was sprayed onto the polyethylene powder to deactivate the catalyst and the co-catalyst.
[0544] (Example 2)
[0545] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X B ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y B ), thereby obtaining polyethylene powder (B).
[0546] The polyethylene powder (B) had a viscosity average molecular weight of 900,000 and a median particle size of 99 μm.
[0547] Table 1 shows the results of the various evaluations performed on the polyethylene powder (B) and the microporous membrane of the polyethylene powder (B) produced by the above-mentioned [Method for producing microporous membrane].
[0548] <(3) Ethylene polymers (X B ) >
[0549] The same method as in Example 1 was used except that the supply amount of hydrogen was adjusted to 16 mol%. A ) was polymerized in the same manner to obtain an ethylene polymer (X BThe obtained ethylene polymer (X B ) had a viscosity average molecular weight of 900,000. The polymerization activity in the first-stage polymerization reactor was 13,000 g per 1 g of the catalyst.
[0550] <(4) Ethylene polymers (Y B ) >
[0551] The same method as in Example 1 was used except that the stirring speed was adjusted to 550 rpm and the supply amount of hydrogen was adjusted to 2 mol%. A ) was polymerized in the same manner to obtain an ethylene polymer (Y B ).
[0552] The obtained ethylene polymer (Y B ) had a viscosity average molecular weight of 900,000. The polymerization activity in the second-stage polymerization reactor was 15,900 g per 1 g of the catalyst.
[0553] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (B).
[0554] (Example 3)
[0555] <(5) Polymerization of polyethylene powder (C)>
[0556] Polymerization of polyethylene powder was carried out using a container-type 300L polymerization reactor with a stirring blade with three retreating blades and three baffles. N-hexane as a solvent was supplied at a flow rate of 40L / hour, the total liquid volume was adjusted in a manner that the slurry concentration was 40% by mass, and the stirring speed was set to 550rpm. Ziegler-Natta catalyst (B) was used as a polymerization catalyst, and was supplied in a manner that made the production rate of polyethylene powder 13kg / hour. In the polymerization catalyst, STATSAFE3000 (90g / L) diluted with n-hexane was added in an amount of 20 mass ppm relative to the production rate of polyethylene powder. Triisobutylaluminum and diisobutylaluminum hydride (9:1 mixture) were used as co-catalyst components and supplied at 10 mmol / hour. 2.9 mol% (molar ratio: hydrogen / (ethylene+hydrogen)) of hydrogen was supplied. The polymerization temperature was set to 78°C, the polymerization pressure was set to 0.3MPaG, and the average residence time was set to 3.0 hours. The polymerization slurry in the polymerization reactor was introduced into a flash tank at a pressure of 0.05 MPaG and a temperature of 70°C in such a manner that the liquid level in the polymerization reactor was kept constant, and unreacted ethylene and hydrogen were separated in the flash tank. Next, the polymerization slurry was continuously sent from the flash tank to a centrifugal separator by a pump to separate the polymer from the solvent, and then the separated polyethylene powder was sent to a rotary kiln type dryer controlled at 90°C and dried while spraying nitrogen. It should be noted that in this drying process, steam was sprayed onto the polyethylene powder to deactivate the catalyst and the co-catalyst.
[0557] The polyethylene powder (C) obtained in this manner had a viscosity average molecular weight of 900,000 and a median particle size of 110 μm. The polymerization activity in the polymerization reactor was 20,000 g per 1 g of the catalyst.
[0558] Table 1 shows the results of the various evaluations performed on the polyethylene powder (C) and the microporous membrane of the polyethylene powder (C) produced by the above-mentioned [Method for producing microporous membrane].
[0559] (Example 4)
[0560] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X D ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y D ), thereby obtaining a polyethylene powder (D). The polyethylene powder (D) had a viscosity average molecular weight of 300,000 and a median particle size of 105 μm.
[0561] Table 1 shows the results of the various evaluations performed on the polyethylene powder (D) and the microporous membrane of the polyethylene powder (D) produced by the above-mentioned [Method for producing microporous membrane].
[0562] <(6) Ethylene polymers (X D ) >
[0563] The same method as in Example 1 was used except that the polymerization catalyst was changed to a Ziegler-Natta catalyst (C). A ) was polymerized in the same manner to obtain an ethylene polymer (X D The obtained ethylene polymer (X D ) had a viscosity average molecular weight of 300,000. The polymerization activity in the first-stage polymerization reactor was 11,500 g per 1 g of the catalyst.
[0564] <(7) Ethylene polymers (Y D ) >
[0565] Compared with the above (Example 1) (Y A ) was polymerized in the same manner to obtain an ethylene polymer (Y D The obtained ethylene polymer (Y D ) had a viscosity average molecular weight of 300,000. The polymerization activity in the second-stage polymerization reactor was 14,000 g per 1 g of the catalyst.
[0566] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (D).
[0567] (Example 5)
[0568] <(8) Polymerization of polyethylene powder (E)>
[0569] Polymerization was carried out in the same manner as above (Example 3) except that the flow rate of n-hexane was adjusted to 80 L / hour, the production rate was adjusted to 10 kg / hour, the slurry concentration was adjusted to 16 mass %, and the average residence time was adjusted to 1.75 hours, thereby obtaining polyethylene powder (E).
[0570] The polyethylene powder (E) obtained in this manner had a viscosity average molecular weight of 900,000 and a median particle size of 108 μm. The polymerization activity in the polymerization reactor was 19,000 g per 1 g of the catalyst.
[0571] Table 1 shows the results of the various evaluations performed on the polyethylene powder (E) and the microporous membrane of the polyethylene powder (E) produced by the above-mentioned [Method for producing microporous membrane].
[0572] [Example 6]
[0573] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X F ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y F ), thereby obtaining polyethylene powder (F).
[0574] The polyethylene powder (F) had a viscosity average molecular weight of 300,000 and a median particle size of 95 μm.
[0575] Table 1 shows the results of the various evaluations performed on the polyethylene powder (F) and the microporous membrane of the polyethylene powder (F) produced by the above-mentioned [Method for producing microporous membrane].
[0576] <(9) Ethylene polymers (X F ) >
[0577] Compared with the above (Example 1) (X A ) was polymerized in the same manner to obtain an ethylene polymer (X F The obtained ethylene polymer (X F ) had a viscosity average molecular weight of 300,000. The polymerization activity in the first-stage polymerization reactor was 12,000 g per 1 g of the catalyst.
[0578] <(10) Ethylene polymer (Y F ) >
[0579] The same method as in Example 1 was used except that the slurry concentration was adjusted to 30% by mass and the stirring speed was adjusted to 230 rpm. A ) was polymerized in the same manner to obtain an ethylene polymer (Y F The obtained ethylene polymer (Y F ) had a viscosity average molecular weight of 300,000. The polymerization activity in the second-stage polymerization reactor was 14,500 g per 1 g of the catalyst.
[0580] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (F).
[0581] (Example 7)
[0582] <(11) Polymerization of polyethylene powder (G)>
[0583] Polymerization was carried out in the same manner as in Example 3, except that the production rate was 9 kg / hour, the slurry concentration was 30 mass %, and the hydrogen supply amount was 1 mol %, thereby obtaining a polyethylene powder (G).
[0584] The polyethylene powder (G) obtained in this manner had a viscosity average molecular weight of 2,000,000 and a median particle size of 103 μm. The polymerization activity in the polymerization reactor was 18,000 g per 1 g of the catalyst.
[0585] Table 1 shows the results of the various evaluations performed on the polyethylene powder (G) and the microporous membrane of the polyethylene powder (G) produced by the above-mentioned [Method for producing microporous membrane].
[0586] (Example 8)
[0587] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X H ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y H ), thereby obtaining polyethylene powder (H). The viscosity average molecular weight of the polyethylene powder (H) was 900,000, and the median particle size was 99 μm. The results of the various evaluations performed on the polyethylene powder (H) and the microporous membrane of the polyethylene powder (H) produced by the above-mentioned [Process for producing microporous membrane] are shown in Table 1.
[0588] <(12) Ethylene polymers (X H ) >
[0589] The same method as in Example 2 was used except that the stirring speed was adjusted to 300 rpm and the slurry concentration was adjusted to 30% by mass. B ) was polymerized in the same manner to obtain an ethylene polymer (X H The obtained ethylene polymer (X H ) had a viscosity average molecular weight of 900,000. The polymerization activity in the first-stage polymerization reactor was 13,000 g per 1 g of the catalyst.
[0590] <(13) Ethylene polymers (Y H ) >
[0591] Except that the stirring speed was adjusted to 450 rpm, the same as in Example 2 (Y B ) was polymerized in the same manner to obtain an ethylene polymer (Y H The obtained ethylene polymer (Y H ) had a viscosity average molecular weight of 900,000. The polymerization activity in the second-stage polymerization reactor was 15,900 g per 1 g of the catalyst.
[0592] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (H).
[0593] (Comparative Example 1)
[0594] <(14) Polymerization of polyethylene powder (I)>
[0595] Polymerization was carried out in the same manner as in the above (Example 5) except that the stirring speed was adjusted to 230 rpm and the polymerization catalyst was changed to the Ziegler-Natta catalyst (E), thereby obtaining a polyethylene powder (I).
[0596] The polyethylene powder (I) obtained in this manner had a viscosity average molecular weight of 900,000 and a median particle size of 111 μm.
[0597] The polymerization activity in the polymerization reactor was 18,000 g per 1 g of the catalyst.
[0598] Table 2 shows the results of the various evaluations performed on the polyethylene powder (I) and the microporous membrane of the polyethylene powder (I) produced by the above-mentioned [Method for producing microporous membrane].
[0599] (Comparative Example 2)
[0600] <(15) Polymerization of polyethylene powder (J)>
[0601] Polymerization was carried out in the same manner as in the above (Example 3) except that the polymerization catalyst was changed to the Ziegler-Natta catalyst (D), thereby obtaining a polyethylene powder (J).
[0602] The polyethylene powder (J) obtained in this manner had a viscosity average molecular weight of 900,000 and a median particle size of 113 μm. The polymerization activity in the polymerization reactor was 18,500 g per 1 g of the catalyst.
[0603] Table 2 shows the results of the various evaluations performed on the polyethylene powder (J) and the microporous membrane of the polyethylene powder (J) produced by the above-mentioned [Method for producing microporous membrane].
[0604] (Comparative Example 3)
[0605] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X K ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y K ), thereby obtaining polyethylene powder (K).
[0606] The polyethylene powder (K) had a viscosity average molecular weight of 900,000 and a median particle size of 94 μm.
[0607] Table 2 shows the results of the various evaluations performed on the polyethylene powder (K) and the microporous membrane of the polyethylene powder (K) produced by the above-mentioned [Method for producing microporous membrane].
[0608] <(16) Ethylene polymers (X K ) >
[0609] The same method as in Example 2 was used except that the stirring speed was adjusted to 450 rpm and the slurry concentration was adjusted to 30% by mass. B ) was polymerized in the same manner to obtain an ethylene polymer (X K ).
[0610] The obtained ethylene polymer (X K ) had a viscosity average molecular weight of 900,000. The polymerization activity in the first-stage polymerization reactor was 12,500 g per 1 g of the catalyst.
[0611] <(17) Ethylene polymers (Y K ) >
[0612] The same method as in Example 2 was used except that the stirring speed was adjusted to 230 rpm and the slurry concentration was adjusted to 20% by mass. B ) was polymerized in the same manner to obtain an ethylene polymer (Y K The obtained ethylene polymer (Y K ) had a viscosity average molecular weight of 900,000. The polymerization activity in the second-stage polymerization reactor was 15,400 g per 1 g of the catalyst.
[0613] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (K).
[0614] (Comparative Example 4)
[0615] <(18) Polymerization of polyethylene powder (L)>
[0616] Polymerization was carried out in the same manner as in the above (Example 5) except that the stirring speed was adjusted to 230 rpm and the polymerization catalyst was changed to the Ziegler-Natta catalyst (D), thereby obtaining a polyethylene powder (L).
[0617] The polyethylene powder (L) obtained in this manner had a viscosity average molecular weight of 900,000 and a median particle size of 99 μm. The polymerization activity in the polymerization reactor was 19,000 g per 1 g of the catalyst.
[0618] Table 2 shows the results of the various evaluations performed on the polyethylene powder (L) and the microporous membrane of the polyethylene powder (L) produced by the above-mentioned [Method for producing microporous membrane].
[0619] (Comparative Example 5)
[0620] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X M ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y M ), thereby obtaining polyethylene powder (M).
[0621] The polyethylene powder (M) had a viscosity average molecular weight of 600,000 and a median particle size of 87 μm.
[0622] Table 2 shows the results of the various evaluations performed on the polyethylene powder (M) and the microporous membrane of the polyethylene powder (M) produced by the above-mentioned [Method for producing microporous membrane].
[0623] <(16) Ethylene polymers (X M ) >
[0624] The same method as in Example 2 was used except that the flow rate of n-hexane was adjusted to 20 L / hour, the slurry concentration was adjusted to 40 mass %, the polymerization catalyst was changed to a Ziegler-Natta catalyst (F), the production rate was adjusted to 13 kg / hour, the supply amount of hydrogen was adjusted to 6 mol %, the polymerization temperature was adjusted to 80° C., and the polymerization pressure was adjusted to 0.5 MPaG. B ) was polymerized in the same manner to obtain an ethylene polymer (X M ).
[0625] The obtained ethylene polymer (X M ) had a viscosity average molecular weight of 800,000. The polymerization activity in the first-stage polymerization reactor was 70,000 g per 1 g of the catalyst.
[0626] <(17) Ethylene polymers (Y M ) >
[0627] The same method as in Example 2 was used except that the stirring speed was adjusted to 230 rpm, the production speed was adjusted to 7 kg / hour, the supply amount of hydrogen was adjusted to 25 mol%, the polymerization temperature was adjusted to 80°C, and the polymerization pressure was adjusted to 0.5 MPaG. B ) was polymerized in the same manner to obtain an ethylene polymer (Y M The obtained ethylene polymer (Y M) had a viscosity average molecular weight of 150,000. The polymerization activity in the second-stage polymerization reactor was 38,000 g per 1 g of the catalyst.
[0628] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (M).
[0629] (Comparative Example 6)
[0630] As shown below, in the polymerization reactor of the first stage, the ethylene polymer (X N ), and polymerized in a polymerization reactor in the second stage to obtain an ethylene polymer (Y N ), thereby obtaining polyethylene powder (N).
[0631] The polyethylene powder (N) had a viscosity average molecular weight of 600,000 and a median particle size of 89 μm.
[0632] Table 2 shows the results of the various evaluations performed on the polyethylene powder (N) and the microporous membrane of the polyethylene powder (N) produced by the above-mentioned [Method for producing microporous membrane].
[0633] <(16) Ethylene polymers (X N ) >
[0634] The same method as in the above-mentioned (Comparative Example 5) was used except that the polymerization catalyst was changed to the Ziegler-Natta catalyst (G). M ) was polymerized in the same manner to obtain an ethylene polymer (X N ).
[0635] The obtained ethylene polymer (X N ) had a viscosity average molecular weight of 800,000. The polymerization activity in the first-stage polymerization reactor was 70,000 g per 1 g of the catalyst.
[0636] <(17) Ethylene polymers (Y N ) >
[0637] Compared with the above (Comparative Example 5) (Y M ) was polymerized in the same manner to obtain an ethylene polymer (Y N The obtained ethylene polymer (Y N ) had a viscosity average molecular weight of 150,000. The polymerization activity in the second-stage polymerization reactor was 38,000 g per 1 g of the catalyst.
[0638] The polymerization slurry in the polymerization reactor was subjected to the same separation and drying operations as those in the above (Example 1) to obtain a polyethylene powder (N).
[0639]
[0640]
[0641] This application is based on the Japanese patent application (Japanese Patent Application No. 2020-196103) filed with the Japan Patent Office on November 26, 2020, the contents of which are incorporated into this application as a reference.
[0642] Industrial Applicability
[0643] The polyethylene powder of the present invention has industrial applicability as a raw material for various molded bodies, microporous films, battery separators, and fibers.
Claims
1. A polyethylene powder, wherein The viscosity average molecular weight of the polyethylene powder is 300,000 or more and 10,000,000 or less, and when a three-component approximation is performed on a free induction decay curve obtained by a Carr Purcell Meiboom Gill method in pulse NMR, the relaxation time T of each component and the abundance ratio R of each component satisfy the following <requirement (1)> and <requirement (2)>, <Requirements (1)> At 180° C., the entanglement index determined by the following (Formula I) is 12 milliseconds or more and 25 milliseconds or less, (Tangle Index) = T α ×R α / (R α +R β )+T β ×R β / (R α +R β )......(Formula I) T α : relaxation time of the component α with low mobility, the unit of the relaxation time is milliseconds, R α : The abundance ratio of the component α with low mobility, the unit of the abundance ratio is %, T β : relaxation time of the component β with medium mobility, the unit of relaxation time is milliseconds, R β : The abundance ratio of the component β having intermediate motility, the unit of the abundance ratio is %, <Requirement (2)> At 180°C, the ratio of the component having intermediate mobility determined by the following (Formula II) is 0.25 or more and 0.5 or less, (Ratio of components with medium mobility) = R β / (R α +R β )……(Formula II) The relaxation time T and the abundance ratio R are obtained by curve fitting the free induction decay obtained by the fourth pulse NMR measurement using the function represented by the following <Formula 1>: <Formula 1> f(t)=R α exp(-t / T α )+R β exp(-t / T β )+R γ exp(-t / T γ ) Among them, R α +R β +R γ =100, t: variable, i.e. the time elapsed from the start of the pulse radiation T α : relaxation time of the component α with low mobility, the unit of the relaxation time is milliseconds, R α : The abundance ratio of the component α with low mobility, the unit of the abundance ratio is %, T β : relaxation time of the component β with medium mobility, the unit of relaxation time is milliseconds, R β : The proportion of the component β with medium mobility, the unit of the proportion is %, T γ : relaxation time of the highly mobile component γ, the unit of the relaxation time is milliseconds, R γ : The abundance ratio of the component γ having high mobility, the unit of the abundance ratio is %.
2. The polyethylene powder according to claim 1, wherein The entanglement index obtained from (Formula I) is 13 milliseconds or more and 22 milliseconds or less.
3. The polyethylene powder according to claim 1 or 2, wherein: The entanglement index obtained from (Formula I) is 14 milliseconds or more and 20 milliseconds or less.
4. The polyethylene powder according to claim 1 or 2, wherein The entanglement index obtained from (Formula I) is 17 milliseconds or more and 20 milliseconds or less.
5. The polyethylene powder according to claim 1 or 2, wherein: The ratio of the component having intermediate motility obtained from (Formula II) is 0.25 or more and 0.45 or less.
6. The polyethylene powder according to claim 1 or 2, wherein: The ratio of the component having intermediate mobility obtained from (Formula II) is 0.3 or more and 0.4 or less.
7. The polyethylene powder according to claim 1 or 2, wherein: The ratio of the component having intermediate mobility obtained from (Formula II) is 0.3 or more and 0.35 or less.
8. The polyethylene powder according to claim 1 or 2, wherein: The abundance ratio R of the components obtained by applying a three-component approximation to the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR is: The change rate of the abundance ratio of the component with low mobility at 180°C is -5% or more and 10% or less, The change rate of the abundance ratio of the component with low mobility at 180°C is calculated by the following (Formula III): (Rate of change in abundance ratio of components with low mobility) = ((R α4 -R α1 ) / R α1 )×100……(Formula III) R α1 : The presence ratio of component α with low motility at the first measurement R α4 : The abundance ratio of the component α with low motility at the fourth measurement.
9. The polyethylene powder according to claim 8, wherein The change rate of the abundance ratio of the component with low mobility at 180° C. is not less than −2% and not more than 8%.
10. The polyethylene powder according to claim 8, wherein The change rate of the abundance ratio of the component with low mobility at 180° C. is 0% to 6%.
11. The polyethylene powder according to claim 1 or 2, wherein: The abundance ratio R of the components obtained by applying a three-component approximation to the free induction decay curve obtained by the Carr Purcell Meiboom Gill method in pulse NMR is: The change rate of the abundance ratio of the component with high mobility at 180° C. is 0% or more and 50% or less, The change rate of the abundance ratio of the component with high mobility at 180°C is calculated by the following (Formula IV): (Ratio of change in abundance of components with high mobility) = ((R γ4 -R γ1 ) / R γ1 )×100……(Formula IV) R γ1 : The abundance ratio of the highly mobile component γ in the first measurement R γ4 : The abundance ratio of the component γ with high mobility in the fourth measurement.
12. The polyethylene powder according to claim 11, wherein The change rate of the abundance ratio of the component with high mobility at 180° C. is 10% or less.
13. The polyethylene powder according to claim 11, wherein The change rate of the abundance ratio of the component with high mobility at 180° C. is 5% or less.
14. The polyethylene powder according to claim 1 or 2, wherein: The isothermal crystallization time of the polyethylene powder at 125° C. is 5 minutes or less.
15. The polyethylene powder according to claim 14, wherein The isothermal crystallization time of the polyethylene powder at 125° C. is 4.5 minutes or less.
16. The polyethylene powder according to claim 14, wherein The isothermal crystallization time of the polyethylene powder at 125° C. is 4 minutes or less.
17. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has a viscosity average molecular weight of 300,000 or more and 3,000,000 or less.
18. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has a viscosity average molecular weight of 300,000 or more and 2,000,000 or less.
19. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder has a median particle size of 50 μm or more and 250 μm or less.
20. The polyethylene powder according to claim 19, wherein The polyethylene powder has a median particle size of 60 μm or more and 200 μm or less.
21. The polyethylene powder according to claim 19, wherein The polyethylene powder has a median particle size of 70 μm or more and 150 μm or less.
22. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is composed of ethylene polymers.
23. The polyethylene powder according to claim 22, wherein The ethylene-based polymer is an ethylene homopolymer or a copolymer of ethylene and other comonomers copolymerizable with ethylene.
24. The polyethylene powder according to claim 23, wherein The other comonomers are one or more selected from α-olefins, vinyl compounds and non-conjugated polyenes.
25. The polyethylene powder according to claim 24, wherein The α-olefin is an α-olefin having 3 to 20 carbon atoms.
26. The polyethylene powder according to claim 24 or 25, wherein The α-olefin is selected from propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene and 1-tetradecene.
27. The polyethylene powder of claim 24, wherein: The vinyl compound is selected from vinylcyclohexane and styrene.
28. The polyethylene powder of claim 24, wherein The non-conjugated polyene is selected from 1,5-hexadiene and 1,7-octadiene.
29. The polyethylene powder according to claim 1 or 2, wherein: The polyethylene powder is used for a battery separator.
30. The method for producing a polyethylene powder according to any one of claims 1 to 29, which is a method for polymerizing ethylene using a polymerization catalyst comprising a carrier having macropores and being easily broken, wherein: The manufacturing method meets the following four conditions: <Condition 1> A step of bringing the polymerization catalyst into contact with a thickener before the polymerization step, or a catalyst transport step of adjusting the pressure difference between a transport source and a transport destination to 0.1 MPa or more and 0.5 MPa or less; <Condition 2> A polymerization step comprising a prepolymerization step or a slurry concentration adjusted to 10 mass % or more and 30 mass % or less, a stirring speed of 100 rpm or more and 300 rpm or less, and a polymerization pressure of 0.6 MPa or more and 2.0 MPa or less; <Condition 3> A polymerization step comprising adjusting the slurry concentration to 30 mass % or more and 60 mass % or less and the stirring speed to 300 rpm or more and 600 rpm or less; <Condition 4> The step indicated by <Condition 3> is placed after the step indicated by <Condition 2>.
31. A molded body, wherein The molded body is a molded body of the polyethylene powder according to any one of claims 1 to 29.
32. The molded article according to claim 31, wherein The molded body is a microporous membrane.
33. The molded article according to claim 31, wherein The shaped body is a fiber.
34. The molded article according to claim 31, wherein The molded body is a battery separator.
35. The molded article according to claim 34, wherein The battery separator is a separator for lithium-ion secondary batteries.
36. The molded article according to claim 34, wherein The battery separator is a lead-acid battery separator.
37. The method for producing a molded product according to any one of claims 31 to 36, wherein The method for producing the molded body includes the steps of extruding a resin using a wet extrusion method, stretching, extracting, and drying.
Citation Information
Patent Citations
PROCESS FOR THE PRODUCTION OF POLYOLEFINS AND THEIR COPOLYMERISATS
DE3127133A1
Steam treating apparatus of block like fiber
JP1982082558A
Metal ion source
JP1983040743A
Polyolefin resin, film, microporous film and battery separator
JP2018090744A
Polyethylen powder
JP2019019265A